Microbial oil production by Yarrowia lipolytica strains using glycerol as carbon source - Elisa Duarte Guerra Coelho; Fernanda Palladino; Elisa A. A. Teixeira; Fernanda L. C. Oliveira; Vânya M. D. Pasa; Luiz H. Rosa; Carlos A. Rosa (Brazilian Journal of Microbiology, 2026)
Yeasts can produce microbial oil from hydrophobic substrates such as glycerol, a byproduct of the biodiesel industry that is often undervalued in the market. Yarrowia lipolytica is capable of degrading glycerol and is considered a model organism for studying lipid accumulation. Different yeast strains and culture conditions can result in varying lipid yields with distinct fatty acid profiles. Thus, in this study, five strains of Y. lipolytica were tested for microbial oil production using pure glycerol at temperatures of 15 °C and 25 °C. None of the isolates were considered oleaginous at 15 °C. However, at 25 °C, the isolates UFMG-CM-Y6114 (from cheese), UFMG-CM-Y4187 (from beach sand), and UFMG-CM-Y6189 (from Antarctica) produced more than 20% lipid content (29.30%, 26.95%, and 34.38%, respectively). No significant differences in lipid content were observed between the UFMG-CM-Y6114 and UFMG-CM-Y4187 strains. The cheese- and Antarctica-derived strains were further tested for their ability to accumulate oil when grown on crude glycerol. Among them, UFMG-CM-Y6189 showed the best performance, producing 9.40 g·L⁻¹ of biomass, 1.90 g·L⁻¹ of lipid yield, and 21.56% lipid content, while consuming 61.3 g·L⁻¹ of glycerol. The fatty acid profile of these lipids was predominantly monounsaturated (59.5%), with oleic acid (49.4%) as the main component. This, combined with a low polyunsaturated fatty acid content (5.2%), makes these lipids particularly suitable for biodiesel production. Therefore, the lipids from the Y. lipolytica strain UFMG-CM-Y6189 represent a promising raw material for biodiesel production from glycerol.

Intestinal Histomorphometric Alterations During Experimental Strongyloidiasis in Mice Treated with Rosmarinus officinalis Essential Oil - Lorena Q. A. Tanaka; Kamilla A. M. Dutra; Nicolas M. H. da Silva; Izadora M. Assis; Gabriela A. C. Duarte; João B. A. Souza; Eleuza R. Machado; Ana Paula S. Perez; Rosângela M. Rodrigues (Acta Parasitologica, 2026)
Purpose Strongyloidiasis is an intestinal helminthiasis that can induce structural alterations in the intestinal mucosa during infection. The present study evaluated histomorphometric alterations of the small intestine in mice experimentally infected with Strongyloides venezuelensis and treated with Rosmarinus officinalis essential oil. Methods Infected animals were treated orally with R. officinalis essential oil (200 or 400 mg/kg), ivermectin or control treatments. Histomorphometric parameters of the small intestine were evaluated, including villus height, epithelial height, crypt depth, muscular layer thickness, brush border height and goblet cell counts. Parasitological parameters were also assessed to characterize the infection model. Results Histomorphometric analysis demonstrated that treatment with essential oil at 200 mg/kg was associated with recovery of villus and epithelial height, increased brush border and goblet cell numbers, as well as attenuation of muscular layer hypertrophy, suggesting preservation of mucosal structure during infection. The 400 mg/kg dose, although associated with greater reduction in parasite burden, was accompanied by increased crypt depth, indicating more intense proliferative remodeling of the intestinal mucosa. Ivermectin promoted the greatest reduction in parasite burden with marked elimination of eggs and females. Conclusion These findings indicate that R. officinalis essential oil modulates intestinal mucosal architecture during experimental strongyloidiasis and highlight its potential influence on host intestinal responses during infection.

Associations between teat apex, milk microbiota, and udder health in primiparous cows: Effects of decontamination in a low biomass context - José A. Ferronatto; Eduardo M. Ramos-Sanchez; Erika K. Ganda; Marcos B. Heinemann; Juliano L. Gonçalves; Marcos V. dos Santos; Julia A. Arantes; Vinicius S. Duarte; Alessandro S. Guimarães; Marcio C. Costa; Marie Joossens; Sarne De Vliegher; et al. (Research in Veterinary Science, 2026)

Effects of high- and low-phenolic pea and field bean residues at contrasting doses on soil respiration, mineral N dynamics, microbial biomass, and subsequent barley growth - Rafael D. C. Duarte; Sandra Caul; Madeline E. Giles; Eric Paterson; Pietro P. M. Iannetta; Ana M. Gomes; Marta W. Vasconcelos (Plant and Soil, 2026)
Background and aims Legume residues are important organic inputs, but their effects depend on residue chemistry and application rate. This study examined how pea ( Pisum sativum ) and field bean ( Vicia faba ) residues with contrasting phytochemical compositions influenced soil functioning and subsequent barley growth, assessing how residue quality and dose shape soil responses. Methods A sandy loam soil was amended with residues from four legume genotypes with contrasting phytochemical profiles but similar C:N ratios, applied at low (5 t ha⁻ 1 ) and high (20 t ha⁻ 1 ) rates. Unamended and mineral fertilization treatments were included for comparison. Barley was then grown in a microcosm setup for 8 weeks, and soil CO₂ efflux, microbial biomass C, inorganic N dynamics, and plant biomass were assessed. Results High-dose applications substantially increased cumulative CO₂ emissions but led to reduced microbial biomass, lower nitrate availability, and significantly suppressed barley growth, particularly for high-phenolic genotypes. In contrast, low-dose low-phenolic residues increased microbial biomass, promoted nitrification, and supported barley growth comparable with mineral fertilizers. Phenolic-rich residues maintained higher ammonium levels and showed reduced microbial and plant responses, indicating inhibitory effects of certain phytochemicals on soil processes. Conclusion Residue impacts on soil processes and crop performance depend strongly on both phytochemical composition and application rate. Low-phenolic residues applied at moderate doses have positively impacted microbial functioning, nitrogen cycling, and barley biomass, whereas high doses, especially of high-phenolic material, were detrimental to microbial activity and plant growth. Integrating residue chemistry into nutrient management could enhance the sustainability of legume-based cropping systems.

From agro-industrial waste to microbial pigments: advances in production substrates and extraction technologies - J. C. Ramos; A. S. Jabur de Assis; G. M. Pegoraro; T. Mendes Silva; I. C. S. Duarte (Systems Microbiology and Biomanufacturing, 2026)
Microbial pigments have been gaining prominence as sustainable alternatives to synthetic dyes, which are often associated with environmental impacts and potential health risks. A wide range of microorganisms, including bacteria, fungi and yeasts, are capable of producing pigments of industrial interest. Despite their potential, large-scale production still faces challenges related to cultivation costs and, in particular, extraction steps, which traditionally rely on the use of organic solvents and may present low yields and limited sustainability. In this context, the use of agro-industrial residues as alternative nutrient sources for microbial growth and pigment biosynthesis emerges as a promising strategy for sustainable valorisation, contributing to reduced production costs, mitigation of environmental impacts and strengthening of the circular bioeconomy. However, the recovery of microbial pigments remains a technological obstacle, as many of these compounds are intracellular or associated with cellular structures, making extraction and purification challenging and affecting industrial feasibility. To overcome these limitations, recent advances have focused on improving extraction techniques in order to increase yield, purity and sustainability. This review addresses the main microbial pigments and their producers, highlighting the potential of agro-industrial residues for sustainable production. In addition, it synthesises recent advances in extraction strategies, emphasising approaches that combine efficiency, reduced environmental impact and economic viability. In an integrated perspective, the discussion demonstrates that the combination of low-cost substrates and more sustainable extraction technologies represents a promising pathway to expand production and meet the growing demand for natural colourants in the food, cosmetic and pharmaceutical industries.

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) relationships with biochemical markers of tenderness in beef Longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2026)

Veterinary perspectives on biosecurity measures in small-scale farming systems across European countries: Results from a cross-national survey - F. Duarte; J. Prodanov-Radulović; B. Mehmedi; A. Piccirillo; M. Stukelj; E. Kldiashvili; V. Nedosekov; B. Milovanovic; N.D. Ayaz; R. Yildiz; S. Meling; I. Toftaker; et al. (Research in Veterinary Science, 2026)

Racial and ethnic disparities in environmental chemical exposures and hypertensive disorders of pregnancy: The ECHO-wide cohort study - Hongxiu Liu; Amii M. Kress; Emma X. Yu; Xuejuan Ning; Akhgar Ghassabian; Linda G. Kahn; Shilpi Mehta-Lee; Sara Brubaker; Akram Alshawabkeh; John Meeker; Carlos A. Camargo; Shakira F. Suglia; et al. (Environmental Pollution, 2026)

Synthetic cannabinoids in hair: a review of recent findings and analytical methods by LC-MS/MS - Rafaela S. Pereira; Olívia B.O. Moreira; Marcone Augusto L. de Oliveira; Claudiane C. Canuto; Diogo O.C. Lemos; Lucas M. Duarte; Silvana V. Rodrigues (Analytica Chimica Acta, 2026)

Traffic and functional polarization of macrophages in the areas of programmed interdigital cell death in the embryonic chick - G. Moran; C. Duarte-Olivenza; J. M. Hurle; C. I. Lorda-Diez; J. A. Montero (Apoptosis, 2026)
In this study, we show that during digit development, the embryonic limb contains an abundant and widespread population of “resident macrophages” that precede the onset of interdigital cell death responsible for the separation of digit primordia. The use of cultures of interdigital mesoderm at different remodeling stages, and GFP+ transgenic embryos in which the distal part of the autopodium has been surgically replaced by a fragment with identical characteristics from wild-type embryos, indicate that “transient macrophages” are also recruited at the beginning of interdigital death. The expression of the Pu.1 gene in coincidence with the onset of interdigital death suggests that primary yolk-sac macrophages are later complemented by macrophages of hematopoietic origin. Q-PCR analysis revealed a predominant M2/anti-inflammatory gene signature in the interdigits during the whole remodeling process that correlated with an interdigital transcriptome including Csf1 , Il-34 , Igf1 , Igfbp5 , Tgfβ4 ( Tgfβ1 in mammals), P 75 NTR / T nfrsf16 , Hgf , Vegfa , that presumably stabilizes the macrophage M2 phenotype. However, M1-proinflammatory genes, including Tnfα and Tlr4 , are expressed at very low levels prior to the onset of cell death but become up-regulated at the end of tissue remodeling. Together, our findings support the existence of “Tissue-Resident” and “Passenger/Transitory” macrophage populations of distinct origin and molecular profile participating in tissue remodeling processes associated with embryonic morphogenesis.

Ohmic heating-assisted extraction of ginger bioactives: Synergistic impacts on extract composition and on the quality of high-protein milk beverages - Gabrielle P. Vieira; Carolina P.C. Martins; Thaís Regina C. Pereira; Lévison C. Cipriano; Maria B. Goulart; Jonas T. Guimarães; Mônica M. Pagani; Maria Carmela K.H. Duarte; Adriano G. Cruz; Sérgio B. Mano; Eliane T. Mársico; Erick A. Esmerino (Food Research International, 2026)

Unravelling the molecular mechanisms of vegetative-to-reproductive transition in Cynara cardunculus by RNA-Seq analysis - A. Paulino; I. Fernandes; R. C. Pires; A. Usié; A. Faustino; J. Santos; T. Brás; D. Rosa; O. S. Paulo; M. F. Duarte; L. Marum (Plant Molecular Biology, 2026)
Cynara cardunculus inflorescence plays a significant role in cheese manufacturing and human consumption due to the milk-clotting capacity and the production of edible immature capitula. Consequently, it is crucial to understand the complex cellular and molecular processes involved in the development of cardoon flowers. The current study used western wild cardoon in two developmental stages, vegetative and reproductive, to understand the molecular mechanisms mediating cardoon`s vegetative-to-reproductive transition. Transcriptome profiling identified 552 differentially expressed genes (DEGs) between vegetative and reproductive stages, with 321 upregulated in stage 4 (vegetative state) and 231 in stages 5/6 (reproductive state). Gene Ontology (GO) analysis revealed DEGs involved in biological processes such as oxidation-reduction, lipid metabolism, and defense responses. Metabolic pathways, including phenylpropanoid biosynthesis and anther/pollen development, were significantly enriched. Genes associated with lignin formation, flavonoid synthesis, and acetyltransferase activity were upregulated in the vegetative stage. At the same time, those related to flower development and sesquiterpene lactone biosynthesis were prominent in the reproductive stage. Transcription factors, including MADS-box and ethylene-responsive families, were critical in regulating developmental transitions. This study provides comprehensive insights into the morphological, chemical, and molecular dynamics of C. cardunculus across its phenological stages, underscoring the plant’s adaptability and potential for pharmaceutical and industrial applications. The findings highlight the importance of seasonal and developmental timing in optimizing the production of valuable secondary metabolites, such as cynaropicrin.

High meiofaunal diversity in the Azores revealed through DNA metabarcoding - Francesca Leasi; Nuno V. Álvaro; Luiz F. Andrade; Thiago Q. Araújo; Víctor Aramayo; Tom Artois; Will M. Ballentine; Franziska S. Bergmeier; Andrea Z. Botelho; Ariane Buckenmeyer; Ana T. Capucho; Irina Cherneva; et al. (Marine Biodiversity, 2026)
To advance understanding of meiofauna, key components of marine benthic ecosystems, an international team conducted a morphology-based taxonomic survey and workshop around São Miguel, the largest Azorean island, in 2019. The survey yielded critical baseline data on meiofaunal diversity and, despite taxonomic challenges that limited identification of certain taxa, laid a solid foundation for further research. To expand these findings, additional samples were analyzed using DNA metabarcoding, a powerful tool that assesses multiple facets of biodiversity, including richness, community composition, and phylogenetic diversity. Metabarcoding identified 480 meiofaunal amplicon sequence variants across 14 phyla, more than doubling the 180 taxa recorded through morphology alone. Of these, 298 (approximately 62%) belonged to phyla targeted during the morphology-based workshop. A comparison between the two approaches, focusing on clades addressed during the workshop, revealed overlapping but expanded patterns of diversity relative to morphology-based taxonomy. This consistency supports the metabarcoding’s ability to uncover meiofaunal diversity and underscores the importance of integrating both methods to achieve a more comprehensive understanding of biodiversity and ecological patterns. As the first metabarcoding study in the Azores, this work establishes a biodiversity baseline for a remote and understudied region, indicating greater benthic diversity than previously recognized. By revealing the complexity of these understudied ecosystems, this research contributes to document and support conservation of biodiversity in the Azores and emphasizes the need for further exploration of meiofaunal communities in isolated oceanic environments.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Ocean transport and vertical mixing connect Greenland's macroalgae to deep ocean carbon sinks - Daniel F. Carlson; Nobuhiro Suzuki; Ruben Carrasco; Karen Filbee-Dexter; Laura C. Gillard; Paul G. Myers; Ana M. Queirós; Jorge Assis; Carlos M. Duarte; Mikael Sejr; Dorte Krause-Jensen (Science of The Total Environment, 2026)

Conductive materials change the composition and activity of butyrate-degrading enrichment cultures with hydrogen as the main electron shuttle - Cátia S.N. Braga; João C. Sequeira; M. Salomé Duarte; Gilberto Martins; Inês A.C. Pereira; Luciana Pereira; M. Madalena Alves; Andreia F. Salvador (Journal of Environmental Sciences, 2026)

Out of sight, but not out of mind: Key issues regarding seafloor macrolitter monitoring - Georg Hanke; Miquel Canals; Ryota Nakajima; Melanie Bergmann; Francois Galgani; Daoji Li; George Papatheodorou; Christopher Kim Pham; Diva J. Amon; Michela Angiolillo; Lene Buhl-Mortensen; Alessandro Cau; et al. (Marine Pollution Bulletin, 2025)

Geological and geomechanical properties of soft rocks from the Lower Jurassic Vale Das Fontes Formation (Lusitanian Basin, Portugal): an exploratory study - P. F. Moreira; C. F. Rodrigues; L. V. Duarte; J. P. Temporão de Sousa; A. Vega y de La Fuente; A. Maldonado-Zamora; M. J. Lemos de Sousa; H. I. Chaminé (Mediterranean Geoscience Reviews, 2025)

Quantitative summary of nine years of fungicide efficacy data for managing white spot and protecting yield in maize - MonalisaC. De Cól; Karla Braga; AdrianoA.P. Custódio; Marcelo G. Canteri; Lucas H. Fantin; Carlos M. Utiamada; Hércules D. Campos; Dagma D. Silva-Araújo; Rodrigo V. Costa; InêsF.U. Yada; Aildson P. Duarte; Alfredo R. Dias; et al. (Crop Protection, 2025)

The role of Penicillium brevicompactum in bioprocessing plastic and metals from printed circuit boards - Diogo A. Ferreira-Filipe; Marta Carvalho; António J.S. Fernandes; Florinda M. Costa; Carla Patinha; Pedro Pato; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Environmental Pollution, 2025)

Oxygen Supersaturation Could Protect Reef‐Building Corals Against Acute Thermal Stress - Anieka J. Parry; Shannon G. Klein; Alexandra Steckbauer; Max S. Dhillon; Marcelle Muniz Barreto; Victoria C. Golding; Eleonora Re; Silvia Arossa; Manuel Aranda; Carlos M. Duarte (Global Change Biology, 2025)
Ongoing climate change is constraining the availability of molecular oxygen (O 2 ) on coral reefs. The field has recently invested considerable resources to quantify the effects of hypoxia on corals. However, drivers of reef oxygen decline will not only expose corals to more frequent episodes of hypoxia but also limit peak daytime oxygen levels. Here, we test the theory of oxygen‐mediated thermal performance on three reef‐building corals by comparing their thermal thresholds under three bulk seawater oxygen concentrations in low flow conditions: 10 mg O 2 L −1 , 6.5 mg O 2 L −1 , and 2 L −1 . We hypothesized that when the photosynthetic machinery of their microalgal symbionts was impaired, corals in higher oxygen treatments would use oxygen from the bulk water to supplement their heightened metabolic demands under heat stress, thereby increasing their thermal thresholds. The higher oxygen treatments of 10 and 6.5 mg O 2 L −1 increased the median lethal thresholds of two out of three corals by at least 0.4°C, while one species showed no detectable effect. The 10 mg O 2 L −1 treatment increased the thermal threshold of one species by a small but detectable extent of 0.2°C—a small effect, but one that is biologically meaningful given that marine heatwaves often push corals beyond limits by fractions of a degree. Across the three species, the onset of coral mortality coincided with the collapse of microalgal photosynthetic oxygen production, suggesting that reef‐building corals depend on oxygen from the bulk seawater to sustain aerobic metabolism during acute thermal stress. We hypothesize that the extent of this reliance is diffusion‐limited and strongly influenced by flow conditions. We posit that differences in coral susceptibility to heatwaves across reefscapes may be partially explained by oxygen regimes within microhabitats, emphasizing oxygen as a key regulator of reef health alongside temperature.

Sex Drives Intraspecific Scaling of Home Range Size in Mammals - Aline Giroux; Denis Valle; Eliezer Gurarie; Marcus Vinicius Vieira; James D. Forester; Luca Börger; Raissa Sepulvida; Nicole Barbour; Erika G. da Rocha; Julia Oshima; Fernanda C. de Azevedo; Frederico G. Lemos; et al. (Ecology Letters, 2025)
Understanding variation in home range size (HR) provides important insights into the underlying ecological processes driving space use. However, it remains unclear whether the interspecific allometric scaling of mammals' HR can also be consistently observed within species and for both sexes. To address this knowledge gap, we GPS‐tracked 349 resident individuals across Brazil, encompassing 18 mammal species. We estimated individuals' HR and modelled intraspecific variation in HR against body mass (BM) and sex. While males showed a positive allometric scaling similar to interspecific findings reported in the literature (exponent = 1.23), females' BM had no statistically discernible relationship with HR. We suggest that males have greater energetic and evolutionary incentives to expand their HR with increasing BM, and more physical capacity to do so. Traditional studies on HR scaling that disregard individual sex may, in reality, reflect an average of two distinct patterns, while failing to accurately represent either one.

Carbon footprint calculator for the Portuguese textile and clothing industry: development, application and validation - C. Duarte; J. V. Ferreira; I. P. L. Brás; M. E. F. Silva (International Journal of Environmental Science and Technology, 2025)
This study aimed to develop, implement, and validate a carbon footprint (CF) calculator to estimate greenhouse gas (GHG) emissions generated by Portugal´s Textile and Clothing Sector (TCS). To achieve this, the GHG Protocol and life cycle assessment (LCA) methodology were applied to develop the CF and analyse two textile and clothing companies (A and B). Validation was conducted using a self-assessment method that employed 2 online calculators and a LCA software. The CF calculator enables the quantification of the 3 scopes of GHG emissions. Scope 1 includes direct emissions from sources that are owned or controlled by the company, such as on-site energy, transportation of raw materials, finished products and personnel, as well as water usage. Scope 2 comprises indirect emissions from the use of purchased energy and Scope 3 includes emissions that occur across the supply chain, such as public water usage, wastewater, transportation, employee business travel, waste disposal and the end-of-life treatment of sold products. Avoided emissions and carbon offsetting measures and carbon sequestration strategies, were included. For Company A, energy consumption was the largest contributor to the CF, accounting for 76% of the contributions. In Company B, the waste component had the greatest impact on the CF, accounted for 38% of the contributions. In the validation process, the electricity and fuel consumption components yielded values that are consistent with those from other calculators. The calculator is a tool that TCS companies can use to quantify their emissions and define measures to reduce or offset their CF.

Aiding sea turtle conservation through coastal management - Jakob C. Christiaanse; Ad J. H. M. Reniers; Stefan G. J. Aarninkhof; Elias F. Ostertag; Ronel Nel; Carlos M. Duarte; José A. A. Antolínez (Frontiers in Marine Science, 2025)
Climate change and human activity pose increasing challenges to endangered sea turtles, which are key species in many marine ecosystems worldwide. Among these challenges are the flooding and erosion of nesting beaches. In this perspective, we argue that existing methods and tools from coastal science and management hold significant, yet underused, potential for sea turtle conservation. We introduce a stepwise framework for integrating sea turtle ecology and coastal management to address these coastal threats. The framework follows an Observe–Understand–Predict–Intervene cycle and links ecological thresholds, coastal processes, and management interventions across scales, from Regional Management Units (RMUs) to individual beaches. We illustrate how state-of-the-art monitoring, modeling, and nature-based solutions (NBS) can be embedded within this framework to inform when and how to intervene. Increased in-situ data collection and interdisciplinary collaboration will be critical to apply and refine this approach, thereby enhancing the long-term resilience of nesting habitats.

Supramolecular environment and androgen receptor binding of taraxerol: from molecular structure to potential bioactivity function - Lara L. G. C. Rodrigues; Vitor S. Duarte; Antônio S. N. Aguiar; Vitória A. M. Silva; Hamilton B. Napolitano; Leonardo L. Borges (Rendiconti Lincei. Scienze Fisiche e Naturali, 2025)

Exploring intra-specific variation in photosynthesis of maize and sorghum - Rafael L. Almeida; Neidiquele M. Silveira; Heitor L. Sartori; Camila C. Carvalho; Maximiliano S. Scarpari; Aildson P. Duarte; Eduardo Sawazaki; Eduardo C. Machado; Rafael V. Ribeiro (Theoretical and Experimental Plant Physiology, 2025)

Fatty acid profile of Gammarus locusta newly hatched offspring from the wild and from adults farmed on mono-specific macroalgal diets - João P. Sousa; Luísa Marques; Daniela P. Rodrigues; Felisa Rey; Manuel Albuquerque; Maria Rosário M. Domingues; Rafael C. Duarte; Ricardo Calado (Frontiers in Marine Science, 2025)
The accelerated growth of marine aquaculture targeting species that require formulated aquafeeds creates a pressing need to find new sustainable ingredients and additives that can secure a premium farming performance, as well as the nutritional value of farmed species. Marine gammarid amphipods can be an excellent source of essential fatty acids (FA), namely, long-chain n -3 polyunsaturated FA (LC-PUFA). However, their potential contribution to aquaculture feeds remains largely unexplored. The present work evaluated the effect of five mono-specific macroalgal diets ( Ulva sp., Fucus sp., Laminaria sp., Gracilaria sp., and Chondrus sp.) on the FA composition of the offspring of Gammarus locusta fed on these macroalgae and compared it with the offspring of wild conspecifics. Results revealed that offspring from wild G. locusta showed the highest amount of PUFA (4.95 ± 0.31 μg mg -1 DW), as well as essential FA, namely eicosapentaenoic acid (EPA, 20:5 n -3) (2.49 ± 0.21 μg mg -1 DW) and docosahexaenoic acid (DHA, 22:6 n -3) (0.87 ± 0.16 μg mg -1 DW). The treatment with the highest amount of PUFA and EPA was the one using Fucus sp. as a mono-specific macroalgal diet (4.46 ± 0.31 μg mg -1 DW and 2.42 ± 0.24 μg mg -1 DW, respectively). The best levels of DHA in offspring were recorded for specimens feeding on Chondrus sp. (0.56 ± 0.10 μg mg -1 DW). Significant differences in the abundance of stearic acid (18:0) and DHA were observed between the offspring of adults fed algal-based diets and those from the wild. These findings suggest that G. locusta selectively conserves and directly or indirectly biosynthesises essential FA for growth and reproduction, particularly LC-PUFA. Overall, G. locusta can perform a trophic upgrade of its diet, making this gammarid amphipod a promising additive for the formulation of high-quality aquafeeds supplying LC-PUFA.

Cleaning validation in pharmaceutical quality control laboratories: a structured protocol for contamination risk mitigation - Maria J. Moura; André D. Pereira; Daniel J. F. Santos; Ana G. Silva; Carla C. A. D. Paiva; Belmiro P. M. Duarte (DARU Journal of Pharmaceutical Sciences, 2025)
Background Cleaning activities are critical in pharmaceutical manufacturing to prevent cross-contamination of Active Pharmaceutical Ingredients (APIs). Traditionally, cleaning validation protocols have focused on production lines. However, there is a growing trend toward extending these protocols to Quality Control (QC) laboratories, encompassing both glassware and stainless-steel equipment. Objectives This paper presents a systematic approach for developing cleaning validation protocols specifically designed for QC laboratory equipment, aimed at improving cleaning effectiveness and ensuring regulatory compliance. Methods The proposed methodology includes: (i) identifying the worst-case API; (ii) performing recovery studies to optimize sampling methods and solvent selection; and (iii) employing statistical tools such as descriptive analysis and hypothesis testing to refine the protocol in line with current industry standards. Results A case study involving Oxcarbazepine demonstrates the application of the proposed protocol, evaluating surface contamination across various QC instruments and assessing detergent residues to validate cleaning effectiveness. Conclusion The proposed strategy provides a structured, statistically grounded framework for developing cleaning validation protocols in QC laboratories, promoting effective contamination control and adherence to regulatory standards. Graphical abstract

Effects of short-term exposure to elevated atmospheric CO2 on yield, nutritional profile, genetic regulatory pathways, and rhizosphere microbial community of common bean (Phaseolus vulgaris) - Rafael D. C. Duarte; Marta Nunes da Silva; Gianuario Fortunato; Juan Quirós-Vargas; Onno Muller; Célia M. Manaia; Marta W. Vasconcelos (Plant and Soil, 2025)
Aim Legumes are vital to agroecosystems and human nutrition, yet climate change is compromising their nutritional value. This study aims to assess how a one-month exposure to elevated CO 2 (eCO 2 ) impacts biomass yield, mineral profile, gene expression, and the soil microbiome of common bean plants ( Phaseolus vulgaris L.). Methods Phaseolus vulgaris L. was grown in field conditions under ambient CO 2 (control, aCO 2 , 400 ppm) or eCO 2 (600 pm) from the start of pod filling until plant maturity and analyzed for several morphophysiological and nutritional parameters. Results Compared with aCO 2 , eCO 2 exposure significantly increased plant and grain biomass, with fluctuations in mineral accumulation. Notably, it decreased grain iron and zinc concentrations, two essential microelements related to food security, by 59% and 49%, respectively. Additionally, grain phenolic content decreased by up to 41%. Genes involved in mineral uptake (such as FER1 , ZIP1 , and ZIP16 ), plant response to stress ( TCR1 , TCR2 , and HLH54 ) and symbiosis with soil microorganisms ( NRMAP7 and RAM2 ) seemed to regulate effects. Microbiome analysis supported these findings, with an increase in the relative abundance of Pseudomonadota by 10%, suggesting eCO 2 -induced alterations in microbial community structure. Conclusions This research demonstrates how eCO 2 impacts the nutritional quality of common beans regarding micronutrients and phenolic content, while also affecting soil microbiome composition. Highlighting the value of shorter term eCO 2 treatments, the findings provide early insights into immediate plant responses. This underscores the need for crop improvement strategies to address nutrient deficiencies that may arise under future eCO 2 conditions.

Highly Efficient Bio-Based Composites from Natural Fibers for Fauna Protection and Oil Spill Remediation - Islla M. C. Silvino; Beatriz S. Alves; Eduardo J. Fonseca; Vanderson B. Bernardo; Carmem L. P. S. Zanta; Josealdo Tonholo; Laís F. A. M. Oliveira; José L. S. Duarte; Leonardo M. T. M. Oliveira (Environmental Processes, 2025)

Au-TiO2 Catalysts for Enhanced Visible Light Photocatalysis for Sustainable Treatment of Textile Effluents - Raiane dos Santos; Evelle Duarte C. Oliveira; Ivana C. F. Araujo; Jhonanta N. Silva; Alan G. Câmara; Emerson F. M. da Silva; Ramón R. P. Garcia; Daniella C. Napoleão; Luciano C. Almeida (Water, Air, & Soil Pollution, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Monitoring the stability of aerobic granular sludge under increasing fractions of slowly biodegradable substrate using quantitative image analysis - Sérgio A. Silva; M. Salomé Duarte; António L. Amaral; Eugénio C. Ferreira; M. Madalena Alves; Daniela P. Mesquita (Chemosphere, 2025)

Evaluation of rapid evaporative ionization mass spectrometry (REIMS) for the prediction of slice shear force and quality grades in beef longissimus lumborum steaks - Kaitlyn R. Loomas; Dale R. Woerner; Ben M. Bohrer; Tyson R. Brown; Heather L. Bruce; Marcio S. Duarte; Bimol C. Roy; Yifei Wang; Katie Pedgerachny; Jerrad F. Legako (Meat Science, 2025)

Environmental risks of the third re-purposing of the Haber-Bosch reaction - Carlos M. Duarte; William C. Dennison (Environmental Sustainability, 2025)
The Haber-Bosch reaction, using energy to convert nitrogen gas into ammonia, is now being repurposed, fueled by renewable energy, to produce green ammonia. Green ammonia then becomes the carrier of hydrogen energy to fuel a range of processes, including the mobility of vessels and automobiles. Yet, the massive production of ammonia produced by the Haber-Bosch reaction to yield synthetic fertilizer applied to agricultural soils resulted in a major deterioration of water quality and the proliferation of dead zones in freshwater and coastal ecosystems. The combustion of ammonia results in reactive nitrogen species, such as NO x , which is also a potent green-house gas. To ensure that the green ammonia revolution delivers the environmental benefits it is designed to provide it is essential that policy regulations to avoid leakage of ammonia and reactive nitrogen forms to the environment precede its deployment at scale. New technologies are being proposed to further convert these products into inert N 2 , achieving circularity in the production and use of green ammonia, which is essential to avoid unintended environmental impacts.

Differentially spliced mitochondrial CYP419A1 contributes to ethiprole resistance in Nilaparvata lugens - B. Zeng; A.J. Hayward; A. Pym; A. Duarte; W.T. Garrood; S-F Wu; C-F Gao; C. Zimmer; M. Mallott; T.G.E. Davies; R. Nauen; C. Bass; et al. (Insect Biochemistry and Molecular Biology, 2025)

Mapping high-risk areas for Mycobacterium tuberculosis complex bacteria transmission: Linking host space use and environmental contamination - Eduardo M. Ferreira; Mónica V. Cunha; Elsa L. Duarte; António Mira; Daniela Pinto; Inês Mendes; André C. Pereira; Tiago Pinto; Pelayo Acevedo; Sara M. Santos (Science of The Total Environment, 2024)

Innovative waste activated sludge pre-treatment using a raceway pond Reactor: Integration of Low-Temperature and solar radiation - Joana P. Monteiro; C. Cruzeiro; M. Salomé Duarte; M. Alcina Pereira; Vítor J.P. Vilar (Chemical Engineering Journal, 2024)

P15-03 Immunotoxicity as an endpoint: on the lookout for contaminants of emerging concern for drinking water quality - S.M. Shaikh; R. Hoondert; T. Pronk; D. Duarte; A. Reus; C. Houtman; M. Schriks; R. van der Oost; J. Ezendam; R. Pieters; M.M.L. Dingemans (Toxicology Letters, 2024)

P14-06 The cytotoxicity of bortezomib in AC16 cardiac cells and possible therapeutic options involving Nrf2 - C. Vitorino-Oliveira; S. Kahremany; L. Nisim; M. Duarte-Araújo; F. Carvalho; A. Gruzman; V.M. Costa (Toxicology Letters, 2024)

P02-27 PM2.5 organic extract induced toxicity varies between 2D and 3D cultured bronchial epithelial cells - T. Celis; T. Silva; C. Alves; H. Oliveira; I.F. Duarte; P.H. Hoet; M. Ghosh (Toxicology Letters, 2024)

Bacterial septicemia and herpesvirus infection in Antarctic fur seals (Arctocephalus gazella) stranded in the São Paulo coast, Brazil - Aricia Duarte-Benvenuto; A. M. Sánchez-Sarmiento; A. C. Ewbank; R. Zamana-Ramblas; S. Costa-Silva; N. Silvestre; T. Faita; L. B. Keid; R. M. Soares; C. F. Pessi; J. R. Sabbadini; M. F. Borges; et al. (Veterinary Research Communications, 2024)
In August 2021, two juvenile male Antarctic fur seals ( Arctocephalus gazella ) stranded in the southeastern Brazilian coast and were referred to rehabilitation centers. The animals presented increased body temperature, prostration, respiratory distress and despite treatment died. A necropsy following a standardized protocol was performed, and formalin-fixed tissues were processed for microscopic examination. Samples were screened for morbillivirus, herpesvirus, and Brucella spp. by molecular analyses (PCR, RT-PCR). Bacteriological culture was performed in samples collected from the lungs, trachea, and lymph nodes of both cases. The main histopathologic findings were of infectious nature, including multifocal necrotizing and fibrinous mixed interstitial pneumonia, bronchiolitis, and bronchitis, with intralesional myriad bacteria associated with vascular fibrinoid necrosis. Pseudomonas aeruginosa was isolated from tracheal and lung swabs of Case 1, and Klebsiella oxytoca was found in nostril swabs, tracheobronchial lymph nodes, and lung of Case 2. Gammaherpesvirus infection was detected in both cases, and the sequences retrieved were classified into the genus Percavirus . All tested samples were PCR-negative for Brucella spp. and morbillivirus. We hypothesize that the deficient immunological status in association with starvation predisposed the reactivation of herpesvirus and secondary bacterial co-infections. To the authors’ knowledge, this is the first molecular detection of herpesvirus in an Antarctic pinniped. These findings reinforce that Otariid gammaherpesvirus circulating in the Southern Hemisphere are likely endemic in the Arctocephalus genus. This report contributes to the current knowledge of health aspects affecting wild pinnipeds, especially in the poorly studied Antarctic species.

Biodegradation of e-waste microplastics by Penicillium brevicompactum - Diogo A. Ferreira-Filipe; Leila Oliveira; Ana Paço; António J.S. Fernandes; Florinda M. Costa; Armando C. Duarte; Teresa Rocha-Santos; Ana L. Patrício Silva (Science of The Total Environment, 2024)

Zircon U-Pb and Lu-Hf isotopes reveal the crustal evolution of the SW Angolan Shield (Congo Craton) - Ezequiel Ferreira; Jérémie Lehmann; José Feliciano Rodrigues; Ben Hayes; Enrique Merino-Martínez; Lorenzo Milani; Grant M. Bybee; Trishya M. Owen‑Smith; José Luis García-Lobón; Colombo C. G. Tassinari; Henriette Ueckermann; Kei Sato; et al. (Gondwana Research, 2024)

Correction: Increased policy ambition is needed to avoid the effects of climate change and reach carbon removal targets in Portugal - Jiesper Strandsbjerg Tristan Pedersen; Luís Filipe Dias; Kasper Kok; Detlef van Vuuren; Pedro M. M. Soares; Filipe Duarte Santos; João C. Azevedo (Regional Environmental Change, 2024)

Increased policy ambition is needed to avoid the effects of climate change and reach carbon removal targets in Portugal - Jiesper Strandsbjerg Tristan Pedersen; Luís Filipe Dias; Kasper Kok; Detlef van Vuuren; Pedro M. M. Soares; Filipe Duarte Santos; João C. Azevedo (Regional Environmental Change, 2024)
The Paris Agreement’s goal of limiting global warming hinges on forest carbon sequestration as a key in several national strategies. However, Portugal’s rising forest fire occurrences threaten its ability to meet ambitious 2030 and 2050 carbon sequestration targets. Considering fire and forest trends, this study aims to quantify whether Portugal can reach its carbon sequestration ambitions as stated in its 2030 and 2050 targets. We tested three national forest scenario extensions of the global Shared Socioeconomic Pathways (SSPs) and Shared Policy Assumptions (SPAs) based on a dynamic model, simulating forest area and carbon sequestration related to future fire risk and policies of fire management, forest management, restoration of burnt areas, and climate change adaptation. The model projects a rapidly decreasing forest area under existing Portuguese policies (PT-SSP3), a slow decline under moderate policy improvements (PT-SSP2), and an almost stable forest area under long-term sustainable policy developments (PT-SSP1). In PT-SSP3, carbon sequestration will be reduced to 60% by 2050 compared to 2015, while it declines to about 85% and 90% under PT-SSP2 and PT-SSP1, respectively. It is still plausible to reach Portugal’s 2030 sequestration obligations under the EU’s Paris Agreement target under all three scenarios, while the Portuguese GHG neutrality target is not reached in the presented scenarios. Our four introduced policy areas (increasing focus on fire and forest management, forest restoration, and climate change adaptation of forest stands) must be supplemented by other policy strategies, such as reforestation.

Freezing and thawing in Antarctica: characterization of antifreeze protein (AFP) producing microorganisms isolated from King George Island, Antarctica - J. C. Lopes; V. P. Veiga; B. Seminiuk; L. O. F. Santos; A. M. C. Luiz; C. A. Fernandes; C. T. Kinasz; V. H. Pellizari; R. T. D. Duarte (Brazilian Journal of Microbiology, 2024)

Lost in the dark: Antipatharia-Symbiodiniaceae association in the deep waters of the Red Sea - Silvia Vicario; Tullia I. Terraneo; Carolina Bocanegra Castano; Giovanni Chimienti; Nicolas Oury; Silvia Vimercati; Benjamin C. C. Hume; Fabio Marchese; Megan K. B. Nolan; Ameer A. Eweida; Sam J. Purkis; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Black corals (Hexacorallia: Antipatharia) are a major component of mesophotic and deep marine ecosystems. Due to their preference for light deprived environments, black corals have historically been considered azooxanthellate, yet recent works have found them in association with dinoflagellates of the family Symbiodiniaceae down to 396 m depth. While corals and Symbiodiniaceae generally establish a symbiotic relationship in shallow water environments, the implications of this association is less well understood at deeper depths, where low light penetration cannot sustain efficient photosynthetic activity for the algae. However, Symbiodinaceae are not obligate autotrophs, and their capacity for heterotrophic feeding categorizes them as mixotrophs. In this study, we investigated the presence and diversity of Symbiodiniaceae associated with the deep-sea black coral Bathypathes thermophila (Antipatharia: Schizopathidae), collected from 204 to 655 m depth in the Saudi Arabian Red Sea. Using high-throughput sequencing of the ITS2 region, we report (1) the deepest record to date of Symbiodiniaceae associated with an anthozoan from 655 m, and (2) the first Red Sea record of Antipatharia in association with Symbiodiniaceae. Our analyses revealed that 14 out of 27 colonies of B. thermophila were associated with Symbiodiniaceae of the genera Cladocopium and Durusdinium . We unveiled 16 novel ITS2 type profiles, possibly unique to black corals and/or to these depths, along with seven profiles that were already known from shallow-water hard corals. No significant pattern was detected in terms of community diversity in relation to depth or sampling locality. Our study supports the existence of black corals-Symbiodiniaceae association and warrants further research to better understand the evolutionary processes and physiological mechanisms driving this association, specifically in light deprived environments.

Antimicrobial prophylaxis in companion animal surgery: A scoping review for European Network for Optimization of Antimicrobial Therapy (ENOVAT) guidelines - T.M. Sørensen; K. Scahill; J. Espinel Ruperez; M. Olejnik; F. Swinbourne; D.R. Verwilghen; M.C. Nolff; S. Baines; C. Marques; A. Vilen; E.L. Duarte; M. Dias; et al. (The Veterinary Journal, 2024)

Consistent Symbiodiniaceae community assemblage in a mesophotic-specialist coral along the Saudi Arabian Red Sea - Silvia Vimercati; Tullia I. Terraneo; Carolina Bocanegra Castano; Federica Barreca; Benjamin C. C. Hume; Fabio Marchese; Mustapha Ouhssain; Alexandra Steckbauer; Giovanni Chimienti; Ameer A. Eweida; Christian R. Voolstra; Mattie Rodrigue; et al. (Frontiers in Marine Science, 2024)
Introduction The Red Sea is a narrow rift basin characterized by latitudinal environmental gradients which shape the diversity and distribution of reef-dwelling organisms. Studies on Symbiodiniaceae associated with select hard coral taxa present species- specific assemblages and concordant variation patterns from the North to southeast Red Sea coast at depths shallower than 30 m. At mesophotic depths, however, algal diversity studies are rare. Here, we characterize for the first-time host-associated algal communities of a mesophotic specialist coral species, Leptoseris cf. striatus , along the Saudi Arabian Red Sea coast. Methods We sampled 56 coral colonies spanning the eastern Red Sea coastline from the Northern Red Sea to the Farasan Banks in the South, and across two sampling periods, Fall 2020 and Spring 2022. We used Next Generation Sequencing of the ITS2 marker region in conjunction with SymPortal to denote algal assemblages. Results and discussion Our results show a relatively stable coral species-specific interaction with algae from the genus Cladocopium along the examined latitudinal gradient, with the appearance, in a smaller proportion, of presumed thermally tolerant algal taxa in the genera Symbiodinium and Durusdinium during the warmer season (Fall 2020). Contrary to shallow water corals, our results do not show a change in Symbiodiniaceae community composition from North to South in this mesophotic specialist species. However, our study highlights for the first time that symbiont communities are subject to change over time at mesophotic depth, which could represent an important phenomenon to address in future studies.

Marine resource exploitation and human settlement patterns during the Neolithic in SW Europe: stable oxygen isotope analyses (δ18O) on Phorcus lineatus (da Costa, 1778) from Campo de Hockey (San Fernando, Cádiz, Spain) - Asier García-Escárzaga; Juan J. Cantillo-Duarte; Stefania Milano; Rosa Arniz-Mateos; Igor Gutiérrez-Zugasti; Enrique González-Ortegón; Jose M. Corona-Borrego; José Ramos-Muñoz; André C. Colonese; Eduardo Vijande-Vila (Archaeological and Anthropological Sciences, 2024)
In recent decades, investigations in the southern Iberian Peninsula have increased our understanding of the socio-economic impact of the spread of the Neolithic in southwestern Europe, including changes in marine resources exploitation. Nevertheless, considerable uncertainty still exists around the seasonality of such subsistence systems and the putative role of marine fish and shellfish to the evolving agro-pastoral economies. Earlier studies on the European Atlantic coast (including Iberia) have shown that the stable oxygen isotope (δ 18 O) values from the topshell Phorcus lineatus (da Costa, 1778) can be reliably used to derive seasonal sea surface temperatures (SST) during its lifespan. This information can be used by archaeologists to estimate the seasonality of mollusc collection in the past, and to shed light into settlement and subsistence patterns. This paper presents the results of a stable isotope study on archaeological shells of P. lineatus recovered from the Neolithic settlement of Campo de Hockey (Cádiz, Spain). We analysed shells from both funerary and residential contexts and found that P. lineatus was consumed year-round, but with a stronger preference during winter. Our results therefore contribute to advance our understanding of the role of coastal environments in early farming societies of southwestern Europe.

Fibrinonecrotic enteritis and orchitis associated with Salmonella enterica subsp houtenae infection in a short-tailed boa (Boa constrictor amarali) - Raquel M. de Freitas Pereira; Hodias S. de Oliveira Filho; José L. C. Duarte; Fabiano R. P. Júnior; Telma de Sousa Lima; Kin M.O.L. dos Santos; Edivaldo da Silva Pereira; Nádyra Jerônimo da Silva; Celso J. Bruno de Oliveira; Jeann Leal de Araújo; Fábio de Souza Mendonça (Journal of Comparative Pathology, 2024)

Effects of ocean acidification and warming on physiological and behavioural responses of an herbivore snail to waterborne predator cues - S. Benítez; N.A. Lagos; C. Duarte; M. José Cid; J.M. Navarro (Environmental Pollution, 2024)

Facemasks: An insight into their abundance in wetlands, degradation, and potential ecotoxicity - Ana Paço; Ana M. Oliveira; Diogo A. Ferreira-Filipe; Andreia C.M. Rodrigues; Rui J.M. Rocha; Amadeu M.V.M. Soares; Armando C. Duarte; Ana L. Patrício Silva; Teresa Rocha-Santos (Science of The Total Environment, 2023)

Dog in sheep’s clothing: livestock depredation by free-ranging dogs may pose new challenges to wolf conservation - Sofia Lino; Mariana Rossa; Joana M. Fernandes; Tânia Barros; Ana Lino; Dário Hipólito; Eduardo Ferreira; Sara C. Aliácar; Duarte Cadete; Carlos Fonseca; Rita T. Torres; Luís M. Rosalino; et al. (European Journal of Wildlife Research, 2023)
Livestock depredation is a common cause of human-carnivore conflicts. In Portugal, free-ranging dogs are increasingly abundant and overlap endangered Iberian wolf territories, with reports of livestock depredation. However, the lack of awareness about dogs’ possible role as predators leads to bias against wolves in cases of damages. Our goal was to assess and compare wolf and free-ranging dog’s diet composition at southern wolf range in Portugal, to offer insights on dogs’ predatory role on livestock and its implications for the conservation of an endangered wolf subpopulation. We assessed diet composition from 107 to 95 genetically confirmed wolf and dog scats, respectively, and complemented the analysis with data from 40 attacks on livestock with successful genetic predator assignment. Scat analysis highlighted goats as the most consumed dog prey in all analysed regions, with lagomorphs, small mammals, and wild boars as second most consumed in each region, respectively. Wolves mainly relied on goats and wild boars in the west, whereas in the central region they mostly fed on birds. The dietary overlap between both canids was very high (Pianka’s index O = 0.93), showing potential for competition. Additionally, we found that dogs were the sole predators detected in most attacks (62%). Our findings highlight dogs’ role as predators of livestock, and possibly also wild species, posing a further challenge to wolf conservation. Alongside adequate husbandry practices, we emphasise the need for a stronger enforcement of the legislation on dog ownership and an effective management of the stray population to reduce human-wolf conflict.

A common variant close to the “tripwire” linker region of NLRP1 contributes to severe COVID-19 - Vinicius N. C. Leal; Leandro M. Paulino; Raylane A. G. Cambui; Thiago G. Zupelli; Suemy M. Yamada; Leonardo A. T. Oliveira; Valéria de F. Dutra; Carolina B. Bub; Araci M. Sakashita; Ana Paula H. Yokoyama; José M. Kutner; Camila A. Vieira; et al. (Inflammation Research, 2023)

Evidence of hawksbill turtle (Eretmochelys imbricata) depredation on fish caught in gillnets - Yusuf C. El-Khaled; Carlos M. Duarte; Raquel S. Peixoto (Frontiers in Marine Science, 2023)
Bycatch is a major global threat to marine megafauna and occurs in nearly all fishing fleets, including small-scale fisheries that use gillnets. Gillnets represent a threat to endangered air-breathing megafauna, who incidentally entangle in bottom-set gillnets and suffocate after being attracted by bait that is secured on fishing gear. We here provide the first evidence that hawksbill turtles feed on trapped fish in gillnets, suggesting that potential prey items trapped in gillnets may act as additional bait, attracting carnivorous sea turtles towards this threat. This overlooked depredating behaviour potentially explains and increases the likelihood of critically endangered hawksbill turtle bycatch in gillnet fisheries, calling for technological and management solutions.

Subsistence swine farming: seroprevalence and risk factors associated with Lawsonia intracellularis infection in the state of Minas Gerais Brazil in 2016 - J. C. R. Barbosa; R. R. Nicolino; M. P. Gabardo; J. P. M. Gonçalves; M. E. Suarez-Duarte; R. P. Laub; A. G. S. Daniel; G. H. S. Mariano; C. M. Costa; P. A. Correia; M. D. Araújo; R. M. C. Guedes (Tropical Animal Health and Production, 2023)

Intrinsic and specific groundwater vulnerability determination as a pre-operational baseline assessment of an unconventional hydrocarbon industry - G. F. C. Lima; V. G. Ferreira; J. S. D. Lima; J. C. M. Duarte; A. C. Dufilho; C. A. de Carvalho Filho (International Journal of Environmental Science and Technology, 2023)

Current knowledge on the presence, biodegradation, and toxicity of discarded face masks in the environment - Ana M. Oliveira; Ana L. Patrício Silva; Amadeu M.V.M. Soares; Damià Barceló; Armando C. Duarte; Teresa Rocha-Santos (Journal of Environmental Chemical Engineering, 2023)

Evaluating the in vitro digestion of lipids rich in medium-chain fatty acids (MCFAs) using dynamic and static protocols - Ericsem Pereira; Jean-Michel Fernandes; Raquel Gonçalves; Ana C. Pinheiro; M. Salomé Duarte; M. Madalena Alves; Antonio J.A. Meirelles; Guilherme J. Maximo; Antonio A. Vicente (Food Chemistry, 2023)

Norfloxacin prophylaxis effect on multidrug resistance in patients with cirrhosis and bacterial infections - Sebastián Marciano; Maria N. Gutierrez-Acevedo; Sabrina Barbero; Lorena del C. Notari; Marina Agozino; Jose L. Fernandez; Maria M. Anders; Nadia Grigera; Florencia Antinucci; Orlando F. Orozco Ganem; Maria D. Murga; Daniela Perez; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Brain damage serum biomarkers induced by COVID-19 in patients from northeast Brazil - Ryan C. Silva; Michelle M. da Rosa; Heloísa I. Leão; Eduardo D. L. Silva; Nathália T. Ferreira; Amanda P. B. Albuquerque; Gisele S. Duarte; André M. Siqueira; Michelly C. Pereira; Moacyr J. B. M. Rêgo; Maira G. R. Pitta (Journal of NeuroVirology, 2023)

Amazon raw clay as a precursor of a clay-based adsorbent: experimental study and DFT analysis for the adsorption of Basic Yellow 2 dye - Emanuele D. V. Duarte; Wedja T. Vieira; Rodrigo O. Góes; Luiz E. C. de Azevedo; Melissa G. A. Vieira; Meuris G. C. da Silva; Samira M. L. de Carvalho (Environmental Science and Pollution Research, 2023)

Proximity to residential and workplace pesticides application and the risk of progression of Parkinson's diseases in Central California - Shiwen Li; Beate Ritz; Yufan Gong; Myles Cockburn; Aline Duarte Folle; Irish Del Rosario; Yu Yu; Keren Zhang; Emily Castro; Adrienne M. Keener; Jeff Bronstein; Kimberly C. Paul (Science of The Total Environment, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Removing chemical and biological pollutants from swine wastewater through constructed wetlands aiming reclaimed water reuse - Maria L. Bôto; Sofia M. Dias; Rute Duarte Crespo; Ana P. Mucha; C. Marisa R. Almeida (Journal of Environmental Management, 2023)

Bioactive compounds from marine macroalgae in the treatment and prevention of neurodegenerative diseases - M. Fernanda C. Leal; Rúben J. G. Duarte; Inês L. Cardoso; Rita I. L. Catarino; Adriana M. Pimenta; M. Renata S. Souto (Neurophysiology, 2023)

Rock n' Seeds: A database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation - Carlos A. Ordóñez‐Parra; Roberta L. C. Dayrell; Daniel Negreiros; Antônio C. S. Andrade; Letícia G. Andrade; Yasmine Antonini; Leilane C. Barreto; Fernanda de V. Barros; Vanessa da Cruz Carvalho; Blanca Auxiliadora Dugarte Corredor; Antônio Cláudio Davide; Alexandre A. Duarte; et al. (Ecology, 2023)
Advancing functional ecology depends fundamentally on the availability of data on reproductive traits, including those from tropical plants, which have been historically underrepresented in global trait databases. Although some valuable databases have been created recently, they are mainly restricted to temperate areas and vegetative traits such as leaf and wood traits. Here, we present Rock n' Seeds, a database of seed functional traits and germination experiments from Brazilian rock outcrop vegetation, recognized as outstanding centers of diversity and endemism. Data were compiled through a systematic literature search, resulting in 103 publications from which seed functional traits were extracted. The database includes information on 16 functional traits for 383 taxa from 148 genera, 50 families, and 25 orders. These 16 traits include two dispersal, six production, four morphological, two biophysical, and two germination traits—the major axes of the seed ecological spectrum. The database also provides raw data for 48 germination experiments, for a total of 10,187 records for 281 taxa. Germination experiments in the database assessed the effect of a wide range of abiotic and biotic factors on germination and different dormancy‐breaking treatments. Notably, 8255 of these records include daily germination counts. This input will facilitate synthesizing germination data and using this database for a myriad of ecological questions. Given the variety of seed traits and the extensive germination information made available by this database, we expect it to be a valuable resource advancing comparative functional ecology and guiding seed‐based restoration and biodiversity conservation in tropical megadiverse ecosystems. There are no copyright restrictions on the data; please cite this paper when using the current data in publications; also the authors would appreciate notification of how the data are used in publications.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Lionfish on the loose: Pterois invade shallow habitats in the tropical southwestern Atlantic - Marcelo O. Soares; Caroline V. Feitosa; Tatiane M. Garcia; Kelly Ferreira Cottens; Bruno Vinicius; Sandra Vieira Paiva; Oscar de Sousa Duarte; Lívio Moreira Gurjão; Grasielle Dayse de Vasconcelos Silva; Rafaela Camargo Maia; Diego M. Previatto; Pedro B. M. Carneiro; et al. (Frontiers in Marine Science, 2022)
Lionfish ( Pterois spp.) evolved in the Indo-Pacific with predators and prey and invaded regions (e.g., the Caribbean Sea and Mediterranean) where no such balance yet exists. In 2020, four lionfish were recorded on mesophotic reefs of the Amazon offshore Coast and Fernando de Noronha Archipelago. However, until now, there were no records of invasive lionfish in Brazilian nearshore waters or even such a high number of individuals. In this article, we report the continuing invasion process along the Brazilian Province by multiple sightings (72) of lionfish from March to May 2022 in estuaries, seagrass beds, and artificial and natural reefs across 240 km of the Brazilian coast. These are the first records of lionfish in coastal northeast Brazil and the shallowest records (1–16 m) from South Atlantic tropical waters. The largest simultaneous records of lionfish in breakwaters, fishing weirs, and marambaias (artificial reefs used as fishing grounds) on the Brazilian Northeastern coast indicate that these man-made structures are suitable habitats for this species. Most of the lionfish (58%) were recorded in artificial reefs and fishing weirs. Moreover, the detection of invasions in marginal reefs, estuaries, and two marine protected areas characterized by moderately turbid water and high sedimentation rates highlights the adaptability of the lionfish, making it extremely difficult for divers and fishers to capture them. We call for an urgent management plan considering that the invaded tropical region hosts a high level of endemism, and rare and/or cryptic taxa, which increases the risk of impacts since these are primary lionfish prey.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global diversity and distribution of aerobic anoxygenic phototrophs in the tropical and subtropical oceans - Carlota R. Gazulla; Adrià Auladell; Clara Ruiz‐González; Pedro C. Junger; Marta Royo‐Llonch; Carlos M. Duarte; Josep M. Gasol; Olga Sánchez; Isabel Ferrera (Environmental Microbiology, 2022)
Summary The aerobic anoxygenic phototrophic (AAP) bacteria are common in most marine environments but their global diversity and biogeography remain poorly characterized. Here, we analyzed AAP communities across 113 globally‐distributed surface ocean stations sampled during the Malaspina Expedition in the tropical and subtropical ocean. By means of amplicon sequencing of the puf M gene, a genetic marker for this functional group, we show that AAP communities along the surface ocean were mainly composed of members of the Halieaceae (Gammaproteobacteria), which were adapted to a large range of environmental conditions, and of different clades of the Alphaproteobacteria, which seemed to dominate under particular circumstances, such as in the oligotrophic gyres. AAP taxa were spatially structured within each of the studied oceans, with communities from adjacent stations sharing more taxonomic similarities. AAP communities were composed of a large pool of rare members and several habitat specialists. When compared to the surface ocean prokaryotic and picoeukaryotic communities, it appears that AAP communities display an idiosyncratic global biogeographical pattern, dominated by selection processes and less influenced by dispersal limitation. Our study contributes to the understanding of how AAP communities are distributed in the horizontal dimension and the mechanisms underlying their distribution across the global surface ocean.

Global proteomic analysis of the follicular fluid from brown brocket deer (Mazama gouazoubira; Fisher, 1814) - Thais T. S. Souza; Maurício F. van Tilburg; Maria J. B. Bezerra; Luciana D. Rola; Leda M. C. Pereira; José M. B. Duarte; Maiana S. Chaves; Luciana M. Melo; Arlindo A. A. N. Moura; Vicente J. F. Freitas (European Journal of Wildlife Research, 2022)

Trade-offs between succulent and non-succulent epiphytes underlie variation in drought tolerance and avoidance - S. G. Gotsch; C. B. Williams; R. Bicaba; R. Cruz-de Hoyos; A. Darby; K. Davidson; M. Dix; V. Duarte; A. Glunk; L. Green; B. Ferguson; K. Muñoz-Elizondo; et al. (Oecologia, 2022)

Identification of potential new mosquito-associated viruses of adult Aedes aegypti mosquitoes from Tocantins state, Brazil - Matheus A. Duarte; Fabrício S. Campos; Osvaldo F. Araújo Neto; Leonardo A. Silva; Arthur B. Silva; Thalita C. Aguiar; Raissa N. Santos; Ueric J. B. Souza; Giselly B. Alves; Fernando L. Melo; Daniel M. P. Ardisson-Araujo; Raimundo W. S. Aguiar; et al. (Brazilian Journal of Microbiology, 2022)

Euryhalinity and thermal tolerance of Phyllorhiza punctata (Scyphozoa) scyphostomae: life history and physiological trade-offs - Lénia D. Rato; Carlos Pinto; Inês M. Duarte; Sérgio M. Leandro; Sónia C. Marques (Marine Biology, 2021)

Cecropia hololeuca : A new source of compounds with potential anti-inflammatory action - Emanuelle G. Machado; Oswaldo Cardoso; Nerilson M. Lima; Paloma E. Carvalho; Alice D. Barbosa; Guilherme F. S. Sobrinho; Jennifer F. Duarte; Laryssa R. Coelho; Pietra P. C. Soares; Ayane G. Orneles; Ana Carolina B. Santos; Kamila B. Santos; et al. (Natural Product Research, 2021)

Nutrient and temperature constraints on primary production and net phytoplankton growth in a tropical ecosystem - Daffne C. López‐Sandoval; Carlos M. Duarte; Susana Agustí (Limnology and Oceanography, 2021)
The Red Sea depicts a north–south gradient of positively correlated temperature and nutrient concentration. Despite its overall oligotrophic characteristics, primary production rates in the Red Sea vary considerably. In this study, based on five cruises and a 2‐year time series (2016–2018) sampling in the Central Red Sea, we determined phytoplankton photosynthetic rates (PP) by using 13 C as a tracer and derived phytoplankton net growth rates ( μ ) and chlorophyll a (Chl a )‐normalized photosynthesis (P B ). Our results indicate a ninefold variation (14–125 mgC m −2 h −1 ) in depth‐integrated primary production and reveal a marked seasonality in PP, P B , and μ . Depth‐integrated PP remained −2 h −1 during spring and summer, and peaked in autumn–winter, particularly in the southernmost stations (~17°N). In surface waters, phytoplankton grew at a slow rate (0.2 ± 0.02 d −1 ), with the population doubling every 3.5 days, on average. However, during the autumn–winter period, when Chl a concentrations peaked in the central and southern regions, μ increased to values between 0.60 and 0.84 d −1 , while P B reached its maximum rate (7.8 mgC [mg Chl a ] −1 h −1 ). We used path analysis to resolve direct vs. indirect components between correlations. Our results show that nutrient availability modulates the photosynthetic performance and growth of phytoplankton communities and that P B and μ fluctuations are not directly associated with temperature changes. Our study suggests that similarly to other oligotrophic warm seas, phosphorus concentration exerts a key role in defining photosynthetic rates and the biomass levels of phytoplankton communities in the region.

Acarbose presents in vitro and in vivo antileishmanial activity against Leishmania infantum and is a promising therapeutic candidate against visceral leishmaniasis - Rafaella R. Costa; João A. Oliveira-da-Silva; Thiago A. R. Reis; Grasiele S. V. Tavares; Débora V. C. Mendonça; Camila S. Freitas; Daniela P. Lage; Vívian T. Martins; Luciana M. R. Antinarelli; Amanda S. Machado; Raquel S. Bandeira; Fernanda Ludolf; et al. (Medical Microbiology and Immunology, 2021)

In vitro and in silico studies of 8(17),12E,14-labdatrien-18-oic acid in airways smooth muscle relaxation: new molecular insights about its mechanism of action - Edilson B. Alencar Filho; Luciano A. A. Ribeiro; Thiego G. C. Carvalho; Fabrício S. Silva; Luiz Antonio M. S. Duarte-Filho; Euzébio G. Barbosa; Pedro M. N. Menezes; Josean F. Tavares; Marcelo S. da Silva; Bagnólia A. Silva (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Perception of Citizens Regarding Marine Litter Impacts: Collaborative Methodologies in Island Fishing Communities of Cape Verde - José C. Ferreira; Renato Monteiro; Lia Vasconcelos; Cláudio M. Duarte; Filipa Ferreira; Euclides Santos (Journal of Marine Science and Engineering, 2021)
Marine litter has been considered one of the most serious global challenges, requiring urgent action by governmental bodies, especially in African Small Island Developing States (SIDS), where resources and research are limited. In addition to this, waste management and environmental education and ocean literacy programs in schools are scarce, with islands suffering more seriously from these problems. Despite the amount of literature regarding causes and impacts of marine litter, there is still not enough research conducted concerning the public perceptions on both the problem and the potential solutions. This is even more noticeable in African developing countries, where resources and research are scarce. Perception plays a key role for ecosystem management and conservation policies. This study intends to explore the perceptions of local island fishing communities in Cape Verde regarding marine litter, in order to contribute for an improvement of marine ecosystem management and development of conservation policies. To achieve that, two participatory sessions were conducted in two communities in the island of Santiago—Porto Mosquito and Porto Gouveia—where brainstorming and active listening were used to create shared and authentic spaces for dialogue between the members of the community. Results show that the population of both communities were very aware of the marine litter problem. They were able to identify the lack of a proper waste management system in the island and the inappropriate behaviours of the population as the main causes of this problem. Equipment damages and the presence of plastic inside the fish were the most relevant impacts identified by the participants. These findings reinforce previous research on the importance of public engagement and environmental education to contribute to the conservation of marine ecosystems and to build a strong collaborative ocean governance.

Susan Lynn Williams: the Life of an Exceptional Scholar, Leader, and Friend (1951–2018) - William C. Dennison; Matthew E. S. Bracken; Maria Brown; John F. Bruno; James T. Carlton; Robert C. Carpenter; Tim J. B. Carruthers; Megan N. Dethier; Carlos M. Duarte; Thomas R. Fisher; James W. Fourqurean; Richard K. Grosberg; et al. (Estuaries and Coasts, 2021)
Susan Lynn Williams (1951–2018) was an exceptional marine ecologist whose research focused broadly on the ecology of benthic nearshore environments dominated by seagrasses, seaweeds, and coral reefs. She took an empirical approach founded in techniques of physiological ecology. Susan was committed to applying her research results to ocean management through outreach to decision-makers and resource managers. Susan’s career included research throughout the USA in tropical, temperate, and polar regions, but she specialized in tropical marine ecology. Susan’s scholarship, leadership, and friendship touched many people, leading to this multi-authored paper. Susan’s scholarship was multi-faceted, and she excelled in scientific discovery, integration of scientific results, application of science for conservation, and teaching, especially as a mentor to undergraduate and graduate students and postdoctoral scholars. Susan served in a variety of leadership positions throughout her career. She embodied all facets of leadership; leading by example, listening to others, committing to the “long haul,” maintaining trust, and creating a platform for all to shine. Susan was an important role model for women in science. Susan was also a loyal friend, maintaining friendships for many decades. Susan loved cooking and entertaining with friends. This paper provides an overview of the accomplishments of Susan in the broad categories of scholarship, leadership, and friendship.

Reduced cutaneous inflammation associated with antioxidant action after topical application of the aqueous extract of Annona muricata leaves - Luana M. Cercato; Jéssica M. D. Araújo; Alan S. Oliveira; Allan J. O. Melo; Bruno S. Lima; Edmilson W. P. dos Santos; Agenor G. dos S. Neto; Ricardo L. C. de Albuquerque-Júnior; Marcelo C. Duarte; Adriano A. S. Araujo; Ana Mara O. Silva; Renata Grespan; et al. (Inflammopharmacology, 2021)

Microbiome taxonomic and functional profiles of two domestic sewage treatment systems - K. J. Hidalgo; T. Saito; R. S. Silva; Tiago P. Delforno; Iolanda C. S. Duarte; V. M. de Oliveira; Dagoberto Y. Okada (Biodegradation, 2021)

Investing in Blue Natural Capital to Secure a Future for the Red Sea Ecosystems - Maha J. Cziesielski; Carlos M. Duarte; Nojood Aalismail; Yousef Al-Hafedh; Andrea Anton; Faiyah Baalkhuyur; Andrew C. Baker; Thorsten Balke; Iliana B. Baums; Michael Berumen; Vasiliki I. Chalastani; Brendan Cornwell; et al. (Frontiers in Marine Science, 2021)
For millennia, coastal and marine ecosystems have adapted and flourished in the Red Sea’s unique environment. Surrounded by deserts on all sides, the Red Sea is subjected to high dust inputs and receives very little freshwater input, and so harbors a high salinity. Coral reefs, seagrass meadows, and mangroves flourish in this environment and provide socio-economic and environmental benefits to the bordering coastlines and countries. Interestingly, while coral reef ecosystems are currently experiencing rapid decline on a global scale, those in the Red Sea appear to be in relatively better shape. That said, they are certainly not immune to the stressors that cause degradation, such as increasing ocean temperature, acidification and pollution. In many regions, ecosystems are already severely deteriorating and are further threatened by increasing population pressure and large coastal development projects. Degradation of these marine habitats will lead to environmental costs, as well as significant economic losses. Therefore, it will result in a missed opportunity for the bordering countries to develop a sustainable blue economy and integrate innovative nature-based solutions. Recognizing that securing the Red Sea ecosystems’ future must occur in synergy with continued social and economic growth, we developed an action plan for the conservation, restoration, and growth of marine environments of the Red Sea. We then investigated the level of resources for financial and economic investment that may incentivize these activities. This study presents a set of commercially viable financial investment strategies, ecological innovations, and sustainable development opportunities, which can, if implemented strategically, help ensure long-term economic benefits while promoting environmental conservation. We make a case for investing in blue natural capital and propose a strategic development model that relies on maintaining the health of natural ecosystems to safeguard the Red Sea’s sustainable development.

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

Assessing VIIRS capabilities to improve burned area mapping over the Brazilian Cerrado - Filippe L.M. Santos; Renata Libonati; Leonardo F. Peres; Allan A. Pereira; Luiza C. Narcizo; Julia A. Rodrigues; Duarte Oom; José M. C. Pereira; Wilfrid Schroeder; Alberto W. Setzer (International Journal of Remote Sensing, 2020)

Milk yield and composition and body weight of offsprings of mixed-breed goats on semi-arid rangelands with different rainfall - M. J. Flores-Najera; L. I. Vélez-Monroy; J. I. Sánchez-Duarte; V. Cuevas-Reyes; M. Mellado; C. A. Rosales-Nieto (Tropical Animal Health and Production, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Phytochemical Characterization, Bioactivities Evaluation and Synergistic Effect of Arbutus unedo and Crataegus monogyna Extracts with Amphotericin B - Alexandra T. Coimbra; Ângelo F. S. Luís; Maria T. Batista; Susana M. P. Ferreira; Ana Paula C. Duarte (Current Microbiology, 2020)

Melatonin ameliorates oxidative stress and DNA damage of rats subjected to a chemically induced chronic model of Maple Syrup Urine Disease - Leticia B. Wessler; Kely Ise; Isabela C. Lemos; Victoria L. Rezende; Mariane B. Duarte; Adriani P. Damiani; Jade de Oliveira; Vanessa M. de Andrade; Emilio L. Streck (Metabolic Brain Disease, 2020)

10th Anniversary of the European Association for Predictive, Preventive and Personalised (3P) Medicine - EPMA World Congress Supplement 2020 - Olga Golubnitschaja; Ondrej Topolcan; Radek Kucera; Vincenzo Costigliola; M. Akopyan; S. N. Akulov; O Alexandrova; Angel Alonso; Russell J. Andrews; A Assuane Duarte; O. Azarova; Maximilian Babel; et al. (EPMA Journal, 2020)
In 2019, the EPMA celebrated its 10th anniversary at the 5th World Congress in Pilsen, Czech Republic. The history of the International Professional Network dedicated to Predictive, Preventive and Personalised Medicine (PPPM / 3PM) is rich in achievements. Facing the coronavirus COVID-19 pandemic it is getting evident globally that the predictive approach, targeted prevention and personalisation of medical services is the optimal paradigm in healthcare demonstrating the high potential to save lives and to benefit the society as a whole. The EPMA World Congress Supplement 2020 highlights advances in 3P medicine.

Differential thermal tolerance between algae and corals may trigger the proliferation of algae in coral reefs - Andrea Anton; Janna L. Randle; Francisca C. Garcia; Susann Rossbach; Joanne I. Ellis; Michael Weinzierl; Carlos M. Duarte (Global Change Biology, 2020)
Marine heatwaves can lead to rapid changes in entire communities, including in the case of shallow coral reefs the potential overgrowth of algae. Here we tested experimentally the differential thermal tolerance between algae and coral species from the Red Sea through the measurement of thermal performance curves and the assessment of thermal limits. Differences across functional groups (algae vs. corals) were apparent for two key thermal performance metrics. First, two reef‐associated algae species ( Halimeda tuna and Turbinaria ornata ) had higher lethal thermal limits than two coral species ( Pocillopora verrucosa and Stylophora pistillata ) conferring those species of algae with a clear advantage during heatwaves by surpassing the thermal threshold of coral survival. Second, the coral species had generally greater deactivation energies for net and gross primary production rates compared to the algae species, indicating greater thermal sensitivity in corals once the optimum temperature is exceeded. Our field surveys in the Red Sea reefs before and after the marine heatwave of 2015 show a change in benthic cover mainly in the southern reefs, where there was a decrease in coral cover and a concomitant increase in algae abundance, mainly turf algae. Our laboratory and field observations indicate that a proliferation of algae might be expected on Red Sea coral reefs with future ocean warming.

The big picture of field hydrology studies in Brazil - Davi C. D. Melo; Jamil A. A. Anache; Cristiano das N. Almeida; Jaqueline V. Coutinho; Geraldo M. Ramos Filho; Lívia M. P. Rosalem; Natália S. Pelinson; Guilherme L. R. A. Ferreira; Dimaghi Schwamback; Kalyl G. Calixto; João P. G. Siqueira; Jean C. Duarte-Carvajalino; et al. (Hydrological Sciences Journal, 2020)

Degradation of a Sunset Yellow and Tartrazine Dye Mixture: Optimization Using Statistical Design and Empirical Mathematical Modeling - G. E. do Nascimento; V. O. M. Cavalcanti; R. M. R. Santana; D. C. S. Sales; J. M. Rodríguez-Díaz; D. C. Napoleão; M. M. M. B. Duarte (Water, Air, & Soil Pollution, 2020)

Cellular and molecular effects of silymarin on the transdifferentiation processes of LX-2 cells and its connection with lipid metabolism - Caio Mateus Silva; Gustavo Duarte Ferrari; Luciane Carla Alberici; Osmar Malaspina; Karen C. M. Moraes (Molecular and Cellular Biochemistry, 2020)

Non-Cytotoxic Sulfated Heterorhamnan from Gayralia brasiliensis Green Seaweed Reduces Driver Features of Melanoma Metastatic Progression - D. L. Bellan; E. Mazepa; S. M. P. Biscaia; J. P. Gonçalves; C. C. Oliveira; G. R. Rossi; L. G. Ferreira; M. D. Noseda; E. S. Trindade; M. E. R. Duarte; C. R. C. Franco (Marine Biotechnology, 2020)

Recovery of Non-tuberculous Mycobacteria from Water is Influenced by Phenotypic Characteristics and Decontamination Methods - Henry M. Z. Fernandes; Emilyn C. Conceição; Karen M. Gomes; Marley G. da Silva; Rubens C. S. Dias; Rafael S. Duarte (Current Microbiology, 2020)

UN Decade on Ecosystem Restoration 2021–2030—What Chance for Success in Restoring Coastal Ecosystems? - Nathan J. Waltham; Michael Elliott; Shing Yip Lee; Catherine Lovelock; Carlos M. Duarte; Christina Buelow; Charles Simenstad; Ivan Nagelkerken; Louw Claassens; Colin K-C Wen; Mario Barletta; Rod M. Connolly; et al. (Frontiers in Marine Science, 2020)

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Peeling the Otolith of Fish: Optimal Parameterization for Micro-CT Scanning - Jonas E. Vasconcelos-Filho; Felix S. L. Thomsen; Borko Stosic; Antonio C. D. Antonino; Daniel A. Duarte; Richard J. Heck; Rosangela P. T. Lessa; Francisco M. Santana; Beatrice P. Ferreira; Paulo J. Duarte-Neto (Frontiers in Marine Science, 2019)

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

Tomato mottle mosaic virus in Brazil and its relationship with Tm-22 gene - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Lázaro E. P. Peres; Déborah Y. A. C. dos Santos (European Journal of Plant Pathology, 2019)

Evaluation of hydration of cement pastes containing high volume of mineral additions - M. A. S. Anjos; R. Reis; A. Camões; F. Duarte; C. Jesus (European Journal of Environmental and Civil Engineering, 2019)

Mitochondria and the Brain: Bioenergetics and Beyond - Pascale Belenguer; João M. N. Duarte; Patrícia F. Schuck; Gustavo C. Ferreira (Neurotoxicity Research, 2019)

Synthesis and in vitro evaluation of substituted tetrahydroquinoline-isoxazole hybrids as anticancer agents - Fausto M. Güiza; Yenny Bueno Duarte; Stelia C. Mendez-Sanchez; Arnold R. Romero Bohórquez (Medicinal Chemistry Research, 2019)

Global challenges for seagrass conservation - Richard K. F. Unsworth; Len J. McKenzie; Catherine J. Collier; Leanne C. Cullen-Unsworth; Carlos M. Duarte; Johan S. Eklöf; Jessie C. Jarvis; Benjamin L. Jones; Lina M. Nordlund (Ambio, 2019)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Involvement of the Cholinergic Parameters and Glial Cells in Learning Delay Induced by Glutaric Acid: Protection by N-Acetylcysteine - Fernanda Silva Rodrigues; Viviane Nogueira de Zorzi; Marla Parizzi Funghetto; Fernanda Haupental; Alexandra Seide Cardoso; Sara Marchesan; Andréia M. Cardoso; Maria Rosa C. Schinger; Alencar Kolinski Machado; Ivana Beatrice Mânica da Cruz; Marta Maria Medeiros Frescura Duarte; Léder L. Xavier; et al. (Molecular Neurobiology, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Evaluation of the effects of extracts of Maytenus imbricata (Celastraceae) on the treatment of inflammatory and metabolic dysfunction induced by high-refined carbohydrate diet - C. C. Veloso; M. C. Oliveira; V. G. Rodrigues; C. C. Oliveira; L. P. Duarte; M. M. Teixeira; A. V. M. Ferreira; A. C. Perez (Inflammopharmacology, 2019)

Biotechnological tools for the effective management of plastics in the environment - Ana Paço; Jéssica Jacinto; João Pinto da Costa; Patrícia S. M. Santos; Rui Vitorino; Armando C. Duarte; Teresa Rocha-Santos (Critical Reviews in Environmental Science and Technology, 2019)

Spatiotemporal trends of area burnt in the Iberian Peninsula, 1975–2013 - João M. N. Silva; Maria Vanesa Moreno; Yannick Le Page; Duarte Oom; Ioannis Bistinas; José Miguel C. Pereira (Regional Environmental Change, 2019)

Biological treatment of vinasse with yeast and simultaneous production of single-cell protein for feed supplementation - K. C. dos Reis; J. M. Coimbra; W. F. Duarte; R. F. Schwan; C. F. Silva (International Journal of Environmental Science and Technology, 2019)

Effects of hydroelectric turbine noise on the behaviour of Leporinus taeniatus (Characiformes: Anostomidae) in captivity - Marina H. L. Duarte; Rafael M. C. Melo; Marina D. A. Scarpelli; Thiago M. A. Carvalho; Linilson R. Padovese; Nilo Bazzoli; Elizete Rizzo (Journal of Ethology, 2019)

Improvement of Biomethane Production from Sewage Sludge in Co-digestion with Glycerol and Waste Frying Oil, Using a Design of Experiments - J. V. Oliveira; T. Duarte; J. C. Costa; A. J. Cavaleiro; M. A. Pereira; M. M. Alves (BioEnergy Research, 2018)

Stable Isotope (δ13C, δ15N, δ18O, δD) Composition and Nutrient Concentration of Red Sea Primary Producers - Carlos M. Duarte; Antonio Delgado-Huertas; Andrea Anton; Paloma Carrillo-de-Albornoz; Daffne C. López-Sandoval; Susana Agustí; Hanan Almahasheer; Núria Marbá; Iris E. Hendriks; Dorte Krause-Jensen; Neus Garcias-Bonet (Frontiers in Marine Science, 2018)

Aged rats are more vulnerable than adolescents to “ecstasy”-induced toxicity - R. Feio-Azevedo; V. M. Costa; D. J. Barbosa; A. Teixeira-Gomes; I. Pita; S. Gomes; F. C. Pereira; M. Duarte-Araújo; J. A. Duarte; F. Marques; E. Fernandes; M. L. Bastos; et al. (Archives of Toxicology, 2018)

Effects of a nanoemulsion with Copaifera officinalis oleoresin against monogenean parasites of Colossoma macropomum: A Neotropical Serrasalmidae - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; C Solans; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Monogeneans are ectoparasites that may cause losses in production and productivity in the aquaculture of Colossoma macropomum . Chemotherapeutics used in aquaculture usually have major adverse effects on fish; hence, the use of essential oils has been considered advantageous, but these are not soluble in water. Thus, the use of nanostructures to enhance water solubility of compounds and improve bioactivity may be very promising. This study investigated the antiparasitic activity of nanoemulsion prepared with Copaifera officinalis oleoresin (50, 100, 150, 200 and 300 mg/L), against monogenean parasites from the gills of C. macropomum . The particle size distribution and zeta potential suggested that a potentially kinetic stable system was generated. The nanoemulsion from C. officinalis oleoresin achieved high efficacy (100%) at low concentrations (200 and 300 mg/L) after 15 min of exposure. This was the first time that a nanoemulsion was generated from C. officinalis oleoresin using a solvent‐free, non‐heating and low‐energy method. Moreover, this was the first time that an antiparasitic against monogeneans on fish gills, based on nanoemulsion of C. officinalis oleoresin, was tested.

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

High waterborne Mg does not attenuate the toxic effects of Fe, Mn, and Ba on Na+ regulation of Amazonian armored catfish tamoatá (Hoplosternum litoralle) - Rafael M. Duarte; Ana Paula Benaduce; Luciano Garcia; Levy C. Gomes; Adriana Chippari Gomes; Adalberto L. Val; Bernardo Baldisserotto (Environmental Science and Pollution Research, 2018)

Detection of the antiviral activity of epicatechin isolated from Salacia crassifolia (Celastraceae) against Mayaro virus based on protein C homology modelling and virtual screening - P. G. Ferreira; A. C. Ferraz; J. E. Figueiredo; C. F. Lima; V. G. Rodrigues; A. G. Taranto; J. M. S. Ferreira; G. C. Brandão; S. A. Vieira-Filho; L. P. Duarte; C. L. de Brito Magalhães; J. C. de Magalhães (Archives of Virology, 2018)

β-(1→6)-d-glucan secreted during the optimised production of exopolysaccharides by Paecilomyces variotii has immunostimulatory activity - Erica F. Osaku; Rafael A. Menolli; Claudia R. L. de M. Costa; Fernando Henrique G. Tessaro; Renan H. de Melo; Alex E. do Amaral; Péricles A. D. Duarte; Arquimedes Paixão de Santana Filho; Andrea Caroline Ruthes; José Luis da C. Silva; Rosiane G. Mello (Antonie van Leeuwenhoek, 2018)

Nanoemulsion from essential oil of Pterodon emarginatus (Fabaceae) shows in vitro efficacy against monogeneans of Colossoma macropomum (Pisces: Serrasalmidae) - D S S Valentim; J L Duarte; A E M F M Oliveira; R A S Cruz; J C T Carvalho; E C Conceição; C P Fernandes; M Tavares‐Dias (Journal of Fish Diseases, 2018)
Outbreaks of diseases pose a major threat to sustainable aquaculture development worldwide. Application of herbal products to combat parasitic diseases provides an alternative approach for sustainable aquaculture. This study investigated the in vitro antiparasitic effects of an oil‐in‐water nanoemulsion prepared using the essential oil from Pterodon emarginatus , against monogeneans infesting Colossoma macropomum . Gill arches from C. macropomum (47.6 ± 14.5 g and 13.5 ± 1.4 cm) that were naturally parasitized by Anacanthorus spathulatus , Notozothecium janauachensis and Mymarothecium boegeri were immersed in different dispersions of the P. emarginatus nanoemulsions (0, 50, 100, 200, 400 and 600 mg/L). The major compounds presented in the essential oil of P. emarginatus were β‐elemene, β‐caryophyllene and α‐humulene. Characterization of these nanoemulsions showed that they have a small mean droplet size and low polydispersity index, which is concordant with stable systems. In this in vitro trial, the P. emarginatus nanoemulsion concentrations of 100, 200, 400 and 600 mg/L presented 100% helminthic efficacy against monogeneans of the gills of C. macropomum . The highest two concentrations used (400 and 600 mg/L) were seen to immobilize the parasites after only 15 min. Therefore, it would be worthwhile testing these concentrations in therapeutic baths against monogeneans of C. macropomum .

New Tools to Identify the Location of Seagrass Meadows: Marine Grazers as Habitat Indicators - Graeme C. Hays; Teresa Alcoverro; Marjolijn J. A. Christianen; Carlos M. Duarte; Mark Hamann; Peter I. Macreadie; Helene D. Marsh; Michael A. Rasheed; Michele Thums; Richard K. F. Unsworth; Paul H. York; Nicole Esteban (Frontiers in Marine Science, 2018)

Tingenone, a pentacyclic triterpene, induces peripheral antinociception due to cannabinoid receptors activation in mice - C. C. Veloso; R. C. M. Ferreira; V. G. Rodrigues; L. P. Duarte; A. Klein; I. D. Duarte; T. R. L. Romero; A. C. Perez (Inflammopharmacology, 2018)

ATLANTIC MAMMAL TRAITS : a data set of morphological traits of mammals in the Atlantic Forest of South America - Fernando Gonçalves; Ricardo S. Bovendorp; Gabrielle Beca; Carolina Bello; Raul Costa‐Pereira; Renata L. Muylaert; Raisa R. Rodarte; Nacho Villar; Rafael Souza; Maurício E. Graipel; Jorge J. Cherem; Deborah Faria; et al. (Ecology, 2018)
Measures of traits are the basis of functional biological diversity. Numerous works consider mean species‐level measures of traits while ignoring individual variance within species. However, there is a large amount of variation within species and it is increasingly apparent that it is important to consider trait variation not only between species, but also within species. Mammals are an interesting group for investigating trait‐based approaches because they play diverse and important ecological functions (e.g., pollination, seed dispersal, predation, grazing) that are correlated with functional traits. Here we compile a data set comprising morphological and life history information of 279 mammal species from 39,850 individuals of 388 populations ranging from −5.83 to −29.75 decimal degrees of latitude and −34.82 to −56.73 decimal degrees of longitude in the Atlantic forest of South America. We present trait information from 16,840 individuals of 181 species of non‐volant mammals (Rodentia, Didelphimorphia, Carnivora, Primates, Cingulata, Artiodactyla, Pilosa, Lagomorpha, Perissodactyla) and from 23,010 individuals of 98 species of volant mammals (Chiroptera). The traits reported include body mass, age, sex, reproductive stage, as well as the geographic coordinates of sampling for all taxa. Moreover, we gathered information on forearm length for bats and body length and tail length for rodents and marsupials. No copyright restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications. We also request that researchers and teachers inform us of how they are using the data.

Mining noise affects loud call structures and emission patterns of wild black-fronted titi monkeys - M. H. L. Duarte; M. C. Kaizer; R. J. Young; M. Rodrigues; R. S. Sousa-Lima (Primates, 2018)

Communities of arbuscular mycorrhizal fungi under Picconia azorica in native forests of Azores - Catarina Drumonde Melo; Sara Luna; Claudia Krüger; Christopher Walker; Duarte Mendonça; Henrique M. A. C. Fonseca; Maria Jaizme-Vega; Artur Câmara Machado (Symbiosis, 2018)

Diet and body shape changes of pāroko Kelloggella disalvoi (Gobiidae) from intertidal pools of Easter Island - J. Vera‐Duarte; C. A. Bustos; M. F. Landaeta (Journal of Fish Biology, 2017)
This study assesses seasonal variation in the morphology and diet of juveniles and adults of the Easter Island endemic goby Kelloggella disalvoi from intertidal pools during September–October 2015 (spring) and June–July 2016 (winter), utilizing geometric morphometric and gut‐content analyses. A set of 16 landmarks was digitized in 128 individuals. Shape changes related to size changes ( i.e . allometry) were low (18·6%) and were seasonally similar. Body shape changes were mainly dorsoventral (44·2% of variance) and comprised posteroventral displacement of the premaxilla and bending of the body. The latter included vertical displacement of the anterior portion of the first and second dorsal fins and the entire base of the caudal fin. Diets mainly comprised developmental stages of harpacticoid copepods (from eggs to adults), ostracods, isopods, gastropods and bivalves. Also, trophic niche breadth remained constant throughout development and did not vary between seasons. Nonetheless, significant dietary differences were detected in specimens collected during spring (main prey items: harpacticoid copepods and copepod eggs) and winter (harpacticoid copepods and copepod nauplii). Finally, there was weak but significant covariation between diet and morphology: molluscivores were characterized by having an inferior mouth gape, whereas planktivores had an anteriorly directed premaxilla.

ATLANTIC ‐ CAMTRAPS : a dataset of medium and large terrestrial mammal communities in the Atlantic Forest of South America - Fernando Lima; Gabrielle Beca; Renata L. Muylaert; Clinton N. Jenkins; Miriam L. L. Perilli; Ana Maria O. Paschoal; Rodrigo L. Massara; Adriano P. Paglia; Adriano G. Chiarello; Maurício E. Graipel; Jorge J. Cherem; André L. Regolin; et al. (Ecology, 2017)
Our understanding of mammal ecology has always been hindered by the difficulties of observing species in closed tropical forests. Camera trapping has become a major advance for monitoring terrestrial mammals in biodiversity rich ecosystems. Here we compiled one of the largest datasets of inventories of terrestrial mammal communities for the Neotropical region based on camera trapping studies. The dataset comprises 170 surveys of medium to large terrestrial mammals using camera traps conducted in 144 areas by 74 studies, covering six vegetation types of tropical and subtropical Atlantic Forest of South America (Brazil and Argentina), and present data on species composition and richness. The complete dataset comprises 53,438 independent records of 83 species of mammals, includes 10 species of marsupials, 15 rodents, 20 carnivores, eight ungulates and six armadillos. Species richness averaged 13 species (±6.07 SD ) per site. Only six species occurred in more than 50% of the sites: the domestic dog Canis familiaris , crab‐eating fox Cerdocyon thous , tayra Eira barbara , south American coati Nasua nasua , crab‐eating raccoon Procyon cancrivorus and the nine‐banded armadillo Dasypus novemcinctus . The information contained in this dataset can be used to understand macroecological patterns of biodiversity, community, and population structure, but also to evaluate the ecological consequences of fragmentation, defaunation, and trophic interactions.

Zooplankton excretion metabolites stimulate Southern Ocean phytoplankton growth - A. Coello-Camba; M. Llabrés; C. M. Duarte; S. Agustí (Polar Biology, 2017)

Middle-Aged Diabetic Females and Males Present Distinct Susceptibility to Alzheimer Disease-like Pathology - E. Candeias; A. I. Duarte; I. Sebastião; M. A. Fernandes; A. I. Plácido; C. Carvalho; S. Correia; R. X. Santos; R. Seiça; M. S. Santos; C. R. Oliveira; P. I. Moreira (Molecular Neurobiology, 2017)

Temperature regulation of marine heterotrophic prokaryotes increases latitudinally as a breach between bottom‐up and top‐down controls - Xosé Anxelu G. Morán; Josep M. Gasol; Massimo C. Pernice; Jean‐François Mangot; Ramon Massana; Elena Lara; Dolors Vaqué; Carlos M. Duarte (Global Change Biology, 2017)
Planktonic heterotrophic prokaryotes make up the largest living biomass and process most organic matter in the ocean. Determining when and where the biomass and activity of heterotrophic prokaryotes are controlled by resource availability (bottom‐up), predation and viral lysis (top‐down) or temperature will help in future carbon cycling predictions. We conducted an extensive survey across subtropical and tropical waters of the Atlantic, Indian and Pacific Oceans during the Malaspina 2010 Global Circumnavigation Expedition and assessed indices for these three types of controls at 109 stations (mostly from the surface to 4,000 m depth). Temperature control was approached by the apparent activation energy in eV (ranging from 0.46 to 3.41), bottom‐up control by the slope of the log‐log relationship between biomass and production rate (ranging from −0.12 to 1.09) and top‐down control by an index that considers the relative abundances of heterotrophic nanoflagellates and viruses (ranging from 0.82 to 4.83). We conclude that temperature becomes dominant (i.e. activation energy >1.5 eV ) within a narrow window of intermediate values of bottom‐up (0.3–0.6) and top‐down 0.8–1.2) controls. A pervasive latitudinal pattern of decreasing temperature regulation towards the Equator, regardless of the oceanic basin, suggests that the impact of global warming on marine microbes and their biogeochemical function will be more intense at higher latitudes. Our analysis predicts that 1°C ocean warming will result in increased biomass of heterotrophic prokaryoplankton only in waters with

Guanosine Exerts Neuroprotective Effect in an Experimental Model of Acute Ammonia Intoxication - G. F. Cittolin-Santos; A. M. de Assis; P. A. Guazzelli; L. G. Paniz; J. S. da Silva; M. E. Calcagnotto; G. Hansel; K. C. Zenki; E. Kalinine; M. M. Duarte; D. O. Souza (Molecular Neurobiology, 2017)

Bimodal fire regimes unveil a global‐scale anthropogenic fingerprint - Akli Benali; Bernardo Mota; Nuno Carvalhais; Duarte Oom; Lee M. Miller; Manuel L. Campagnolo; José M. C. Pereira (Global Ecology and Biogeography, 2017)
Aim While fire is recognized as an integral part of the Earth system, the ability of humans to shape fire regimes both spatially and temporally remains poorly understood. Our goals were to identify the extent of fire regimes exhibiting two annual fire seasons and to investigate the environmental correlates of such regimes at the global scale. Location All areas of the globe exhibiting relevant fire activity, at 0.5º spatial resolution. Time period 2002‐2012. Major taxa studied (not applicable). Methods The modality of fire seasonality at the global scale was classified using a 10‐year record of satellite‐derived fire activity and model fitting of circular statistical distributions. The main environmental correlates controlling global fire regimes were then analysed over bimodal and unimodal areas using the Kolmogorov–Smirnov test. Results About 25% of the global land surface with relevant fire activity has two significantly distinct fire seasons per year, with at least one of these seasons occurring under sub‐optimal fire weather conditions. In these bimodal areas, population density and the fraction of fires occurring in actively managed land, especially in croplands and pastures, are significantly higher than in neighbouring unimodal areas. Results reveal that through these land‐use and management practices humans have a strong influence on global patterns of fire seasonality. Main conclusions We identified a bimodal seasonality pattern, previously unreported at the global scale, and show that it reveals an anthropogenic fingerprint on fire regimes. Insights into where and when fire is actively employed as a land management tool enhance our understanding of the role of fire in the Earth system, and highlight the need to better understand how fire practices may change in the future.

Ashes from fluidized bed combustion of residual forest biomass: recycling to soil as a viable management option - Nuno C. Cruz; Sónia M. Rodrigues; Lina Carvalho; Armando C. Duarte; Eduarda Pereira; Paul F.A.M. Römkens; Luís A.C. Tarelho (Environmental Science and Pollution Research, 2017)

The defensive behavioral patterns of captive white-lipped and collared peccary (Mammalia, Tayassuidae): an approach for conservation of the species - Selene S. C. Nogueira; Aline M Reis; Stefane G. Marsaro; José M. B. Duarte; Viviana Moreto; Stella G. C. Lima; Thaise S. O. Costa; Sérgio L G Nogueira-Filho (acta ethologica, 2017)

Investigating essential and toxic elements in Antarctic macroalgae using a green analytical method - Rochele S. Picoloto; Rodrigo M. Pereira; Vanize C. Costa; Carla A. Hartwig; Claudio M. P. Pereira; Pio Colepicolo; Fabio A. Duarte; Marcia F. Mesko (Journal of Applied Phycology, 2017)

Tracing of aerosol sources in an urban environment using chemical, Sr isotope, and mineralogical characterization - Regina M. B. O. Duarte; João T. V. Matos; Andreia S. Paula; Sónia P. Lopes; Sara Ribeiro; José Francisco Santos; Carla Patinha; Eduardo Ferreira da Silva; Rosário Soares; Armando C. Duarte (Environmental Science and Pollution Research, 2017)

Entangled fates of holobiont genomes during invasion: nested bacterial and host diversities in Caulerpa taxifolia - S. Arnaud‐Haond; T. Aires; R. Candeias; S. J. L. Teixeira; C. M. Duarte; M. Valero; E. A. Serrão (Molecular Ecology, 2017)
Successful prevention and mitigation of biological invasions requires retracing the initial steps of introduction, as well as understanding key elements enhancing the adaptability of invasive species. We studied the genetic diversity of the green alga Caulerpa taxifolia and its associated bacterial communities in several areas around the world. The striking congruence of α and β diversity of the algal genome and endophytic communities reveals a tight association, supporting the holobiont concept as best describing the unit of spreading and invasion. Both genomic compartments support the hypotheses of a unique accidental introduction in the Mediterranean and of multiple invasion events in southern Australia. In addition to helping with tracing the origin of invasion, bacterial communities exhibit metabolic functions that can potentially enhance adaptability and competitiveness of the consortium they form with their host. We thus hypothesize that low genetic diversities of both host and symbiont communities may contribute to the recent regression in the Mediterranean, in contrast with the persistence of highly diverse assemblages in southern Australia. This study supports the importance of scaling up from the host to the holobiont for a comprehensive understanding of invasions.

Biological and molecular characterization of a putative new potexvirus infecting Senna occidentalis - Jorge A. M. Rezende; Viviana M. Camelo-García; Sónia C. S. Andrade; José E. Buriolla; Elliot W. Kitajima; Ligia M. L. Duarte (Archives of Virology, 2017)

Ovarian cycle of southern brown howler monkey (Alouatta guariba clamitans) through fecal progestin measurement - Thiago Silvestre; Eveline S. Zanetti; José M. B. Duarte; Fernando G. Barriento; Zelinda M. B. Hirano; Júlio C. Souza; Fernando C. Passos (Primates, 2017)

Music supported therapy promotes motor plasticity in individuals with chronic stroke - P. Ripollés; N. Rojo; J. Grau-Sánchez; J. L. Amengual; E. Càmara; J. Marco-Pallarés; M. Juncadella; L. Vaquero; F. Rubio; E. Duarte; C. Garrido; E. Altenmüller; et al. (Brain Imaging and Behavior, 2016)

Prevalence of the genus Cladosporium on the integument of leaf-cutting ants characterized by 454 pyrosequencing - A. P. M. Duarte; M. Ferro; A. Rodrigues; M. Bacci; N. S. Nagamoto; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2016)

Topography‐driven isolation, speciation and a global increase of endemism with elevation - Manuel J. Steinbauer; Richard Field; John‐Arvid Grytnes; Panayiotis Trigas; Claudine Ah‐Peng; Fabio Attorre; H. John B. Birks; Paulo A. V. Borges; Pedro Cardoso; Chang‐Hung Chou; Michele De Sanctis; Miguel M. de Sequeira; et al. (Global Ecology and Biogeography, 2016)
Aim Higher‐elevation areas on islands and continental mountains tend to be separated by longer distances, predicting higher endemism at higher elevations; our study is the first to test the generality of the predicted pattern. We also compare it empirically with contrasting expectations from hypotheses invoking higher speciation with area, temperature and species richness. Location Thirty‐two insular and 18 continental elevational gradients from around the world. Methods We compiled entire floras with elevation‐specific occurrence information, and calculated the proportion of native species that are endemic (‘percent endemism’) in 100‐m bands, for each of the 50 elevational gradients. Using generalized linear models, we tested the relationships between percent endemism and elevation, isolation, temperature, area and species richness. Results Percent endemism consistently increased monotonically with elevation, globally. This was independent of richness–elevation relationships, which had varying shapes but decreased with elevation at high elevations. The endemism–elevation relationships were consistent with isolation‐related predictions, but inconsistent with hypotheses related to area, richness and temperature. Main conclusions Higher per‐species speciation rates caused by increasing isolation with elevation are the most plausible and parsimonious explanation for the globally consistent pattern of higher endemism at higher elevations that we identify. We suggest that topography‐driven isolation increases speciation rates in mountainous areas, across all elevations and increasingly towards the equator. If so, it represents a mechanism that may contribute to generating latitudinal diversity gradients in a way that is consistent with both present‐day and palaeontological evidence.

Cytokines profile and its correlation with endothelial damage and oxidative stress in patients with type 1 diabetes mellitus and nephropathy - Rodrigo M. C. Pestana; Caroline P. Domingueti; Rita C. F. Duarte; Rodrigo B. Fóscolo; Janice S. Reis; Ana Maria S. Rodrigues; Laís B. Martins; Lirlândia P. Sousa; Daniela P. Lage; Cláudia N. Ferreira; Adaliene V. M. Ferreira; Ana P. Fernandes; et al. (Immunologic Research, 2016)

Spartina versicolor Fabre: Another case of Spartina trans-Atlantic introduction? - A. Baumel; M. Rousseau-Gueutin; C. Sapienza-Bianchi; A. Gareil; N. Duong; H. Rousseau; O. Coriton; R. Amirouche; S. Sciandrello; B. Duarte; I. Caçador; J. M. Castillo; et al. (Biological Invasions, 2016)

Advantages and limitations of chemical extraction tests to predict mercury soil-plant transfer in soil risk evaluations - R. J. R. Monteiro; S. M. Rodrigues; N. Cruz; B. Henriques; A. C. Duarte; P. F. A. M. Römkens; E. Pereira (Environmental Science and Pollution Research, 2016)

Biofortification of wheat, rice and common bean by applying foliar zinc fertilizer along with pesticides in seven countries - H. Ram; A. Rashid; W. Zhang; A. P. Duarte; N. Phattarakul; S. Simunji; M. Kalayci; R. Freitas; B. Rerkasem; R. S. Bal; K. Mahmood; E. Savasli; et al. (Plant and Soil, 2016)

Assessing soil erosion risk using RUSLE through a GIS open source desktop and web application - L. Duarte; A. C. Teodoro; J. A. Gonçalves; D. Soares; M. Cunha (Environmental Monitoring and Assessment, 2016)

Comparative study on metal biosorption by two macroalgae in saline waters: single and ternary systems - Paula Figueira; Bruno Henriques; Ana Teixeira; Cláudia B. Lopes; Ana T. Reis; Rui J. R. Monteiro; A. C. Duarte; M. A. Pardal; E. Pereira (Environmental Science and Pollution Research, 2016)

The variation of crustal stretching and different modes of rifting along the Australian southern continental margin - N. Kharazizadeh; W. P. Schellart; J. C. Duarte; M. Hall (Australian Journal of Earth Sciences, 2016)

Ocean acidification induces changes in algal palatability and herbivore feeding behavior and performance - Cristian Duarte; Jorge López; Samanta Benítez; Patricio H. Manríquez; Jorge M. Navarro; Cesar C. Bonta; Rodrigo Torres; Pedro Quijón (Oecologia, 2016)

Rhizopus arrhizus and Fusarium solani Concomitant Infection in an Immunocompromised Host - João N. de Almeida Júnior; Karim Y. Ibrahim; Gilda M. B. Del Negro; Evandro D. Bezerra; Amaro N. Duarte Neto; Marjorie V. Batista; Rinaldo F. Siciliano; Mauro C. Giudice; Adriana L. Motta; Flávia Rossi; Ligia C. Pierrotti; Maristela P. Freire; et al. (Mycopathologia, 2016)

Social immunity of the family: parental contributions to a public good modulated by brood size - Ana Duarte; Sheena C. Cotter; Catherine E. Reavey; Richard J. S. Ward; Ornela De Gasperin; Rebecca M. Kilner (Evolutionary Ecology, 2016)

Does ecophysiological behaviour explain habitat occupation of sympatric Clusia species in a Brazilian Atlantic rainforest? - Ulrich Lüttge; Fabio R. Scarano; Eduardo A. de Mattos; Augusto C. Franco; Fernando Broetto; André T. C. Dias; Heitor M. Duarte; Norbert Uehlein; Tânia Wendt (Trees, 2015)

Potato virus Y infection affects flavonoid profiles of Physalis angulata L. - Alice Nagai; Lígia M. L. Duarte; Alexandre L. R. Chaves; Déborah Y. A. C. dos Santos (Brazilian Journal of Botany, 2015)

A global meta‐analysis of the relative extent of intraspecific trait variation in plant communities - Andrew Siefert; Cyrille Violle; Loïc Chalmandrier; Cécile H. Albert; Adrien Taudiere; Alex Fajardo; Lonnie W. Aarssen; Christopher Baraloto; Marcos B. Carlucci; Marcus V. Cianciaruso; Vinícius de L. Dantas; Francesco de Bello; et al. (Ecology Letters, 2015)
Recent studies have shown that accounting for intraspecific trait variation ( ITV ) may better address major questions in community ecology. However, a general picture of the relative extent of ITV compared to interspecific trait variation in plant communities is still missing. Here, we conducted a meta‐analysis of the relative extent of ITV within and among plant communities worldwide, using a data set encompassing 629 communities (plots) and 36 functional traits. Overall, ITV accounted for 25% of the total trait variation within communities and 32% of the total trait variation among communities on average. The relative extent of ITV tended to be greater for whole‐plant (e.g. plant height) vs. organ‐level traits and for leaf chemical (e.g. leaf N and P concentration) vs. leaf morphological (e.g. leaf area and thickness) traits. The relative amount of ITV decreased with increasing species richness and spatial extent, but did not vary with plant growth form or climate. These results highlight global patterns in the relative importance of ITV in plant communities, providing practical guidelines for when researchers should include ITV in trait‐based community and ecosystem studies.

Antileishmanial activity of compounds produced by endophytic fungi derived from medicinal plant Vernonia polyanthes and their potential as source of bioactive substances - Adriana M. do Nascimento; Mateus Gonçalves Soares; Fernanda K. V. da Silva Torchelsen; Jorge A. Viana de Araujo; Paula S. Lage; Mariana C. Duarte; Pedro H. R. Andrade; Tatiana G. Ribeiro; Eduardo A. F. Coelho; Andréa M. do Nascimento (World Journal of Microbiology and Biotechnology, 2015)

Extreme pH Conditions at a Natural CO2 Vent System (Italy) Affect Growth, and Survival of Juvenile Pen Shells (Pinna nobilis) - Lorena Basso; Iris E. Hendriks; Alejandro B. Rodríguez-Navarro; Maria C. Gambi; Carlos M. Duarte (Estuaries and Coasts, 2015)

Assessing the ecotoxicity of metal nano-oxides with potential for wastewater treatment - V. Nogueira; I. Lopes; T. A. P. Rocha-Santos; M. G. Rasteiro; N. Abrantes; F. Gonçalves; A. M. V. M. Soares; A. C. Duarte; R. Pereira (Environmental Science and Pollution Research, 2015)

Size-Dependent Arsenic Accumulation in Scrobicularia plana in a Temperate Coastal Lagoon (Ria de Aveiro, Portugal) - T. Ereira; J. P. Coelho; A. C. Duarte; M. A. Pardal; M. E. Pereira (Water, Air, & Soil Pollution, 2015)

Recurrent patterns of phylogenetic habitat filtering in woody plant communities across phytogeographically distinct grassland-forest ecotones - V. J. Debastiani; S. C. Muller; J. M. Oliveira; F. S. Rocha; M. C. Sestren-Bastos; L. D. S. Duarte (Community Ecology, 2015)

Catalog of total excitation–emission and total synchronous fluorescence maps with synchronous fluorescence spectra of homologated fluorescent pesticides in large use in Morocco: development of a spectrometric low cost and direct analysis as an alert method in case of massive contamination of soils and waters by fluorescent pesticides - S. Foudeil; H. Hassoun; T. Lamhasni; S. Ait Lyazidi; F. Benyaich; M. Haddad; M. Choukrad; A. Boughdad; M. Bounakhla; H. Bounouira; R. M. B. O. Duarte; A. Cachada; et al. (Environmental Science and Pollution Research, 2015)

Genetic diversity and biogeographical patterns of Caulerpa prolifera across the Mediterranean and Mediterranean/Atlantic transition zone - Elena Varela-Álvarez; Ana C. Balau; Núria Marbà; Julio Afonso-Carrillo; Carlos M. Duarte; Ester A. Serrão (Marine Biology, 2015)

Too much is bad—an appraisal of phytotoxicity of elevated plant-beneficial heavy metal ions - Naser A. Anjum; Harminder P. Singh; M. Iqbal R. Khan; Asim Masood; Tasir S. Per; Asha Negi; Daizy R. Batish; Nafees A. Khan; Armando C. Duarte; Eduarda Pereira; Iqbal Ahmad (Environmental Science and Pollution Research, 2015)

A new species of the oligotrophic genus Ochroconis (Sympoventuriaceae) - K. Samerpitak; A. P. M. Duarte; D. Attili-Angelis; F. C. Pagnocca; G. Heinrichs; A. J. M. M. Rijs; A. Alfjorden; A. H. G. Gerrits van den Ende; S. B. J. Menken; G. S. de Hoog (Mycological Progress, 2015)

Geochemistry, mineralogy, solid-phase fractionation and oral bioaccessibility of lead in urban soils of Lisbon - A. P. Reis; C. Patinha; J. Wragg; A. C. Dias; M. Cave; A. J. Sousa; C. Costa; A. Cachada; E. Ferreira da Silva; F. Rocha; A. Duarte (Environmental Geochemistry and Health, 2014)

Diazoxide Attenuates Autoimmune Encephalomyelitis and Modulates Lymphocyte Proliferation and Dendritic Cell Functionality - N. Virgili; P. Mancera; C. Chanvillard; A. Wegner; B. Wappenhans; M. J. Rodríguez; C. Infante-Duarte; J. F. Espinosa-Parrilla; M. Pugliese (Journal of Neuroimmune Pharmacology, 2014)

Mercury accumulation and tissue-specific antioxidant efficiency in the wild European sea bass (Dicentrarchus labrax) with emphasis on seasonality - C. L. Mieiro; M. Dolbeth; T. A. Marques; A. C. Duarte; M. E. Pereira; M. Pacheco (Environmental Science and Pollution Research, 2014)

Leaf-cutting ants: an unexpected microenvironment holding human opportunistic black fungi - A. P. M. Duarte; D. Attili-Angelis; N. C. Baron; L. C. Forti; F. C. Pagnocca (Antonie van Leeuwenhoek, 2014)

Response of a dung beetle assemblage along a reforestation gradient in Restinga forest - Malva I. M. Hernández; Pedro S. C. S. Barreto; Valderêz H. Costa; Antonio J. Creão-Duarte; Mario E. Favila (Journal of Insect Conservation, 2014)

A Multidisciplinary Approach to Evaluate the Efficiency of a Clean-Up Technology to Remove Mercury from Water - Cláudia B. Lopes; Isabel Lopes; Luciana S. Rocha; Armando C. Duarte; Amadeu M. V. M. Soares; João Rocha; Eduarda Pereira (Bulletin of Environmental Contamination and Toxicology, 2014)

Highly polymorphic microsatellite markers for the Mediterranean endemic fan mussel Pinna nobilis - M. GONZALEZ-WANGUEMERT; J. COSTA; L. BASSO; C. DUARTE; E. SERRÃO; I. HENDRIKS (Mediterranean Marine Science, 2014)
Pinna nobilis is an endemic bivalve of the Mediterranean Sea whose populations have decreased in the last decades due to human pressure; as consequence, it was declared a protected species in 1992. Despite its conservation status, few genetic studies using mitochondrial markers have been published. We report on the isolation and development of 10 microsatellite loci for the fan mussel, Pinna nobilis. All loci (2 di-nucleotide, 5 tri-nucleotide, 2 tetra-nucleotide and 1 penta-nucleotide) are characterized by high polymorphism levels in 76 individuals tested from two populations in Balearic Islands (Spain, Western Mediterranean Sea). Number of alleles ranged from 4 to 24 and expected heterozygosity ranged from 0.4269 to 0.9400. These microsatellites could be very useful to assess the genetic diversity and connectivity patterns of P. nobilis and to establish new conservation strategies.

Efficiency of a cleanup technology to remove mercury from natural waters by means of rice husk biowaste: ecotoxicological and chemical approach - Luciana S. Rocha; I. Lopes; Cláudia B. Lopes; Bruno Henriques; Amadeu M. V. M. Soares; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2014)

Sertulariamarginata (Cnidaria: Hydrozoa) in the Mediterranean: an alien species in expansion? - M.M. GONZÁLEZ-DUARTE; C. MEGINA; M. BETHENCOURT (Mediterranean Marine Science, 2014)
Mature and dense populations of the tropical hydroid species Sertulariamarginata were detected in the Alboran Sea (Western Mediterranean) and in the Atlantic coast of the Strait of Gibraltar. Until now, it had only been recorded in the eastern basin within the Mediterranean Sea.This species has previously been recorded in estuaries and anthropogenichabitats but, in the area studied here, we only found it in natural zones. These observations could indicate an early expansion and naturalization in the Mediterranean Sea. Due to its limited dispersion capacity by its own natural means and the history of its records, the observations provided here support the hypothesis of an arrival and a spread by anthropogenic vectors.A pathway of arrival and dispersion of alien species into the Mediterranean Sea is proposed for future monitoring: from Macaronesia (particularly Canary Islands) to the Atlantic coast of the Strait of Gibraltar and from here into the Mediterranean.

Mercury Bioaccumulation in the Egyptian Mongoose (Herpestes ichneumon): Geographical, Tissue, Gender and Age Differences - S. Rodrigues; J. P. Coelho; V. Bandeira; T. Barros; A. C. Duarte; C. Fonseca; M. E. Pereira (Water, Air, & Soil Pollution, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Cork stoppers as an effective sorbent for water treatment: the removal of mercury at environmentally relevant concentrations and conditions - Cláudia B. Lopes; Joana R. Oliveira; Luciana S. Rocha; Daniela S. Tavares; Carlos M. Silva; Susana P. Silva; Niels Hartog; Armando C. Duarte; E. Pereira (Environmental Science and Pollution Research, 2014)

Climate effects on amphibian distributions depend on phylogenetic resolution and the biogeographical history of taxa - L. D. S. Duarte; C. Both; V. J. Debastiani; M. B. Carlucci; L. O. Gonçalves; L. Cappelatti; G. D. S. Seger; V. A. G. Bastazini; F. T. Brum; E. V. Salengue; J. S. Bernardo‐Silva (Global Ecology and Biogeography, 2014)
Aim Disentangling the effects of climate and historical factors on biodiversity distribution remains a challenge for biogeographers. Here, we provide an analytical framework to discriminate the contributions of contemporary climate and the biogeographical history of taxa to the geographical distributions of phylogenetic lineages. Furthermore, we evaluate the constraint that the biogeographical history of clades exerts on the association between climate and clade distribution, i.e. the historical legacy of climatic effects. As a case study, we analysed the distributions of amphibian lineages across the A mericas. Location The A mericas. Methods We tallied the number of amphibian species per genus in each of 262 ecoregions. Each ecoregion was described by the composition of phylogenetic lineages using phylogenetic fuzzy weighting. The composition of amphibian genera and phylogenetic clades represented the distributions of shallow and deep phylogenetic nodes, respectively. We characterized each ecoregion by the biogeographical history of amphibian taxa and its current climate, whose influences on shallow and deep phylogenetic nodes were analysed using variation partitioning analysis. Results The association between climate and the distributions of deep phylogenetic nodes showed a strong historical legacy, although the distribution of amphibian genera was mostly associated with climate. Hyloidea were associated with a G ondwanan origin and higher annual mean temperatures, whereas other clades (e.g. C audata) were related to a L aurasian origin and higher temperature seasonality. Microhylidae were related to occurrence in the E arly J urassic in G ondwana and recent occurrence in the N eotropics. Main conclusions Biogeographical patterns can be thought of as the net outcome of evolutionary, historical and ecological processes. Although temperature is likely to affect the ecology of amphibians, the effects of climate on the distributions of deep phylogenetic nodes were strongly constrained by the biogeographical history of clades. Nevertheless, local, climatically driven processes are likely to influence the distributions of shallow phylogenetic nodes. The historical biogeography of clades might help to explain the interplay between evolutionary and environmental processes in determining assembly patterns found elsewhere.

BbrizAGL6 Is Differentially Expressed During Embryo Sac Formation of Apomictic and Sexual Brachiaria brizantha Plants - Larissa Arrais Guimarães; Diva Maria de A. Dusi; Simona Masiero; Francesca Resentini; Ana Cristina M. M. Gomes; Érica Duarte Silveira; Lilian Hasegawa Florentino; Júlio Carlyle M. Rodrigues; Lucia Colombo; Vera Tavares de C. Carneiro (Plant Molecular Biology Reporter, 2013)

Lifestyle, dietary factors, and antibody levels to oral bacteria in cancer-free participants of a European cohort study - Dominique S. Michaud; Jacques Izard; Zachary Rubin; Ingegerd Johansson; Elisabete Weiderpass; Anne Tjønneland; Anja Olsen; Kim Overvad; Marie Christine Boutron-Ruault; Françoise Clavel-Chapelon; Laure Dossus; Rudolf Kaaks; et al. (Cancer Causes & Control, 2013)

Taxonomic assessment and enzymes production by yeasts isolated from marine and terrestrial Antarctic samples - A. W. F. Duarte; I. Dayo-Owoyemi; F. S. Nobre; F. C. Pagnocca; L. C. S. Chaud; A. Pessoa; M. G. A. Felipe; L. D. Sette (Extremophiles, 2013)

Mercury bioaccumulation and the population dynamics of Mesopodopsis slabberi (Crustacea: Mysidacea) along a mercury contamination gradient - M. D’Ambrosio; S. C. Marques; U. M. Azeiteiro; M. A. Pardal; E. Pereira; A. C. Duarte; P. G. Cardoso (Ecotoxicology, 2013)

Decomposition and nutrient release in leaves of Atlantic Rainforest tree species used in agroforestry systems - Edivânia M. G. Duarte; Irene M. Cardoso; Thomas Stijnen; Maria Alice F. C. Mendonça; Marino S. Coelho; Reinaldo B. Cantarutti; Thomas W. Kuyper; Ecila M. A. Villani; Eduardo S. Mendonça (Agroforestry Systems, 2013)

Erratum to: NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina R. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

NMDA Preconditioning Attenuates Cortical and Hippocampal Seizures Induced by Intracerebroventricular Quinolinic Acid Infusion - Samuel Vandresen-Filho; Alexandre A. Hoeller; Bruno A. Herculano; Marcelo Duzzioni; Filipe S. Duarte; Tetsadê C. B. Piermartiri; Carina C. Boeck; Thereza C. M. de Lima; José Marino-Neto; Carla I. Tasca (Neurotoxicity Research, 2013)

Sertularia marginata (Cnidaria: Hydrozoa) in the Mediterranean: an alien species in expansion? - M. M. GONZÁLEZ-DUARTE; C. MEGINA; M. BETHENCOURT (Mediterranean Marine Science, 2013)
Mature and dense populations of the tropical hydroid species Sertulariamarginata were detected in the Alboran Sea (Western Mediterranean) and in the Atlantic coast of the Strait of Gibraltar. Until now, it had only been recorded in the eastern basin within the Mediterranean Sea.This species has previously been recorded in estuaries and anthropogenichabitats but, in the area studied here, we only found it in natural zones. These observations could indicate an early expansion and naturalization in the Mediterranean Sea. Due to its limited dispersion capacity by its own natural means and the history of its records, the observations provided here support the hypothesis of an arrival and a spread by anthropogenic vectors.A pathway of arrival and dispersion of alien species into the Mediterranean Sea is proposed for future monitoring: from Macaronesia (particularly Canary Islands) to the Atlantic coast of the Strait of Gibraltar and from here into the Mediterranean.

Competitive Removal of Cd2+ and Hg2+ Ions from Water Using Titanosilicate ETS-4: Kinetic Behaviour and Selectivity - Simão P. Cardoso; Cláudia B. Lopes; Eduarda Pereira; Armando C. Duarte; Carlos M. Silva (Water, Air, & Soil Pollution, 2013)

Anxiogenic-like profile of Wistar adult rats based on the pilocarpine model: an animal model for trait anxiety? - Filipe S. Duarte; Marcelo Duzzioni; Alexandre A. Hoeller; Nayana M. Silva; Andy L. Ern; Tetsade C. Piermartiri; Carla I. Tasca; Elaine C. Gavioli; Tadeu Lemos; Antonio P. Carobrez; Thereza C. M. De Lima (Psychopharmacology, 2013)

Beyond climate change attribution in conservation and ecological research - Camille Parmesan; Michael T. Burrows; Carlos M. Duarte; Elvira S. Poloczanska; Anthony J. Richardson; David S. Schoeman; Michael C. Singer (Ecology Letters, 2013)
There is increasing pressure from policymakers for ecologists to generate more detailed ‘attribution’ analyses aimed at quantitatively estimating relative contributions of different driving forces, including anthropogenic climate change ( ACC ), to observed biological changes. Here, we argue that this approach is not productive for ecological studies. Global meta‐analyses of diverse species, regions and ecosystems have already given us ‘ very high confidence’ [ sensu Intergovernmental Panel on Climate Change ( IPCC )] that ACC has impacted wild species in a general sense. Further, for well‐studied species or systems, synthesis of experiments and models with long‐term observations has given us similarly high confidence that they have been impacted by regional climate change (regardless of its cause). However, the role of greenhouse gases in driving these impacts has not been estimated quantitatively. Should this be an ecological research priority? We argue that development of quantitative ecological models for this purpose faces several impediments, particularly the existence of strong, non‐additive interactions among different external factors. However, even with current understanding of impacts of global warming, there are myriad climate change adaptation options already developed in the literature that could be, and in fact are being, implemented now.

Major inputs and mobility of potentially toxic elements contamination in urban areas - A. Cachada; A. C. Dias; P. Pato; C. Mieiro; T. Rocha-Santos; M. E. Pereira; E. Ferreira da Silva; A. C. Duarte (Environmental Monitoring and Assessment, 2013)

Eriophorum angustifolium and Lolium perenne metabolic adaptations to metals- and metalloids-induced anomalies in the vicinity of a chemical industrial complex - Naser A. Anjum; Iqbal Ahmad; Sónia M. Rodrigues; Bruno Henriques; Nuno Cruz; Cláudia Coelho; Mário Pacheco; Armando C. Duarte; Eduarda Pereira (Environmental Science and Pollution Research, 2013)

Seasonal and air mass trajectory effects on dissolved organic matter of bulk deposition at a coastal town in south-western Europe - Patrícia S. M. Santos; Eduarda B. H. Santos; Armando C. Duarte (Environmental Science and Pollution Research, 2013)

Derivation of soil to plant transfer functions for metals and metalloids: impact of contaminant’s availability - S. M. Rodrigues; E. Pereira; A. C. Duarte; P. F. A. M. Römkens (Plant and Soil, 2012)

Hematological indices and activity of NTPDase and cholinesterase enzymes in rats exposed to cadmium and treated with N-acetylcysteine - Jamile F. Gonçalves; Marta M. M. F. Duarte; Amanda M. Fiorenza; Roselia M. Spanevello; Cinthia M. Mazzanti; Roberta Schmatz; Margarete D. Bagatini; Fabiane G. Antes; Pauline Costa; Fátima H. Abdalla; Valderi L. Dressler; Vera M. Morsch; et al. (BioMetals, 2012)

Pesticide application to agricultural fields: effects on the reproduction and avoidance behaviour of Folsomia candida and Eisenia andrei - M. J. G. Santos; M. F. L. Ferreira; A. Cachada; A. C. Duarte; J. P. Sousa (Ecotoxicology, 2012)

Evaluation of Species-Specific Dissimilarities in Two Marine Fish Species: Mercury Accumulation as a Function of Metal Levels in Consumed Prey - C. L. Mieiro; J. P. Coelho; M. Pacheco; A. C. Duarte; M. E. Pereira (Archives of Environmental Contamination and Toxicology, 2012)

Hg transfer from contaminated soils to plants and animals - S. M. Rodrigues; B. Henriques; A. T. Reis; A. C. Duarte; E. Pereira; P. F. A. M. Römkens (Environmental Chemistry Letters, 2012)

Sodium Fluxes in Tamoatá, Hoplosternum litoralle, Exposed to Formation Water from Urucu Reserve (Amazon, Brazil) - Bernardo Baldisserotto; Luciano O. Garcia; Ana Paula Benaduce; Rafael M. Duarte; Thiago L. Nascimento; Levy C. Gomes; Adriana R. Chippari Gomes; Adalberto L. Val (Archives of Environmental Contamination and Toxicology, 2012)

Differential Sex, Morphotype and Tissue Accumulation of Mercury in the Crab Carcinus maenas - Sónia Costa; Ivan Viegas; Eduarda Pereira; Armando C. Duarte; Carlos M. Palmeira; Miguel A. Pardal (Water, Air, & Soil Pollution, 2011)

Vascular endothelial growth factor-A165 (VEGF-A165) stimulates the in vitro development and oocyte competence of goat preantral follicles - V. R. Araújo; G. M. Silva; A. B. G. Duarte; D. M. Magalhães; A. P. Almeida; R. F. B. Gonçalves; J. B. Bruno; T. F. P. Silva; C. C. Campello; A. P. R. Rodrigues; J. R. Figueiredo (Cell and Tissue Research, 2011)

Determination and Evaluation of the Mineral Composition of Obi (Cola acuminate) - Valdinei S. Martins; Raildo M. de Jesus; Erik G. P. da Silva; Wallace Duarte Fragoso; Sérgio L. C. Ferreira (Biological Trace Element Research, 2011)

TRY – a global database of plant traits - J. KATTGE; S. DÍAZ; S. LAVOREL; I. C. PRENTICE; P. LEADLEY; G. BÖNISCH; E. GARNIER; M. WESTOBY; P. B. REICH; I. J. WRIGHT; J. H. C. CORNELISSEN; C. VIOLLE; et al. (Global Change Biology, 2011)
Plant traits – the morphological, anatomical, physiological, biochemical and phenological characteristics of plants and their organs – determine how primary producers respond to environmental factors, affect other trophic levels, influence ecosystem processes and services and provide a link from species richness to ecosystem functional diversity. Trait data thus represent the raw material for a wide range of research from evolutionary biology, community and functional ecology to biogeography. Here we present the global database initiative named TRY, which has united a wide range of the plant trait research community worldwide and gained an unprecedented buy‐in of trait data: so far 93 trait databases have been contributed. The data repository currently contains almost three million trait entries for 69 000 out of the world's 300 000 plant species, with a focus on 52 groups of traits characterizing the vegetative and regeneration stages of the plant life cycle, including growth, dispersal, establishment and persistence. A first data analysis shows that most plant traits are approximately log‐normally distributed, with widely differing ranges of variation across traits. Most trait variation is between species (interspecific), but significant intraspecific variation is also documented, up to 40% of the overall variation. Plant functional types (PFTs), as commonly used in vegetation models, capture a substantial fraction of the observed variation – but for several traits most variation occurs within PFTs, up to 75% of the overall variation. In the context of vegetation models these traits would better be represented by state variables rather than fixed parameter values. The improved availability of plant trait data in the unified global database is expected to support a paradigm shift from species to trait‐based ecology, offer new opportunities for synthetic plant trait research and enable a more realistic and empirically grounded representation of terrestrial vegetation in Earth system models.

Dinucleotide microsatellite markers in the genus Caulerpa - Elena Varela-Álvarez; Travis C. Glenn; Ester A. Serrão; Carlos M. Duarte; Beatriz Martínez-Daranas; Myriam Valero; Núria Marbá (Journal of Applied Phycology, 2011)

Plant diaspore traits as indicators of mutualistic interactions in woody vegetation patches developing into a grassland-forest mosaic - L. Duarte; M. Carlucci; C. Fontana; S. Hartz; V. Pillar (Community Ecology, 2011)

Steady-state level of epidermal growth factor (EGF) mRNA and effect of EGF on in vitro culture of caprine preantral follicles - Juliana Jales H. Celestino; Jamily B. Bruno; Márcia Viviane A. Saraiva; Rebeca M. P. Rocha; Ivina R. Brito; Ana Beatriz G. Duarte; Valdevane R. Araújo; Cleidson M. G. Silva; Maria Helena T. Matos; Claudio C. Campello; José Roberto V. Silva; José Ricardo Figueiredo (Cell and Tissue Research, 2011)

The small nuclear ribonucleoprotein U1A interacts with NS5 from yellow fever virus - Roberta V. M. Bronzoni; Maria C. F. S. Madrid; Danilo V. B. Duarte; Vanessa O. A. Pellegrini; Carolina C. Pacca; Ana C. V. Carmo; Cleslei F. Zanelli; Sandro R. Valentini; Carolina Santacruz-Pérez; João A. R. G. Barbosa; Carol S. Lutz; Paula Rahal; et al. (Archives of Virology, 2011)

Kinetics of Mercury Accumulation and Its Effects on Ulva lactuca Growth Rate at Two Salinities and Exposure Conditions - Sónia Costa; Daniel Crespo; Bruno M. G. Henriques; Eduarda Pereira; Armando C. Duarte; Miguel A. Pardal (Water, Air, & Soil Pollution, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Effect of statins on outcomes in immunosuppressed patients with bloodstream infection - D. Viasus; C. Gudiol; N. Fernández-Sabé; I. Cabello; C. Garcia-Vidal; M. Cisnal; R. Duarte; M. Antonio; J. Carratalà (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

The role of arctic zooplankton in biogeochemical cycles: respiration and excretion of ammonia and phosphate during summer - M. Alcaraz; R. Almeda; A. Calbet; E. Saiz; C. M. Duarte; S. Lasternas; S. Agustí; R. Santiago; J. Movilla; A. Alonso (Polar Biology, 2010)

Are Great Tits (Parus major) Inhabiting the Vicinity of a Pulp Mill Healthy? Impacts on Physiology and Breeding Performance - Ana Cláudia Norte; B. C. Sheldon; J. P. Sousa; P. C. Tavares; M. E. Pereira; A. C. Duarte; J. A. Ramos (Archives of Environmental Contamination and Toxicology, 2010)

Feeding preferences of the sandhopper Orchestoidea tuberculata: the importance of algal traits - C. Duarte; J. M. Navarro; K. Acuña; I. Gómez (Hydrobiologia, 2010)

Antioxidant system breakdown in brain of feral golden grey mullet (Liza aurata) as an effect of mercury exposure - C. L. Mieiro; I. Ahmad; M. E. Pereira; A. C. Duarte; M. Pacheco (Ecotoxicology, 2010)

Seasonality of vegetation fires as modified by human action: observing the deviation from eco‐climatic fire regimes - Yannick Le Page; Duarte Oom; João M. N. Silva; Per Jönsson; José M. C. Pereira (Global Ecology and Biogeography, 2010)
Aim In any region affected, fires exhibit a strong seasonal cycle driven by the dynamic of fuel moisture and ignition sources throughout the year. In this paper we investigate the global patterns of fire seasonality, which we relate to climatic, anthropogenic, land‐cover and land‐use variables. Location Global, with detailed analyses from single 1°× 1° grid cells. Methods We use a fire risk index, the Chandler burning index (CBI), as an indicator of the ‘natural’, eco‐climatic fire seasonality, across all types of ecosystems. A simple metric, the middle of the fire season, is computed from both gridded CBI data and satellite‐derived fire detections. We then interpret the difference between the eco‐climatic and observed metrics as an indicator of the human footprint on fire seasonality. Results Deforestation, shifting cultivation, cropland production or tropical savanna fires are associated with specific timings due to land‐use practices, sometimes largely decoupled from the CBI dynamics. Detailed time series from relevant locations provide comprehensive information about these practices and how they are adapted to eco‐climatic conditions. Main conclusions We find a great influence of anthropogenic activities on global patterns of fire seasonality. The specificity of the main fire practices and their easy identification from global observation is a potential tool to support land‐use monitoring efforts. Our results should also prove valuable in the development of a methodological approach for improving the representation of anthropogenic fire practices in dynamic global vegetation models.

Genetic similarity among genotypes of sugarcane estimated by SSR and coefficient of parentage - L. S. C. Duarte Filho; P. P. Silva; J. M. Santos; G. V. S. Barbosa; C. E. Ramalho-Neto; L. Soares; J. C. F. Andrade; C. Almeida (Sugar Tech, 2010)

Subtidal stromatolites from the Sinemurian of the Lusitanian Basin (Portugal) - Ana C. Azerêdo; Ricardo L. Silva; Luís V. Duarte; M. Cristina Cabral (Facies, 2010)

Genetic structure in the Mediterranean seagrass Posidonia oceanica : disentangling past vicariance events from contemporary patterns of gene flow - I. A. SERRA; A. M. INNOCENTI; G. DI MAIDA; S. CALVO; M. MIGLIACCIO; E. ZAMBIANCHI; C. PIZZIGALLI; S. ARNAUD-HAOND; C. M. DUARTE; E. A. SERRAO; G. PROCACCINI (Molecular Ecology, 2010)

Effects of ECF-Kraft pulp mill effluent treated with fungi (Rhizopus oryzae) on reproductive steroids and liver CYP1A of exposed goldfish (Carassius auratus) - M. S. Diniz; I. Peres; L. Castro; A. C. Freitas; T. A. P. Rocha-Santos; P. M. Costa; R. Pereira; A. C. Duarte (Ecotoxicology, 2009)

Mercury pollution in Ria de Aveiro (Portugal): a review of the system assessment - M. E. Pereira; A. I. Lillebø; P. Pato; M. Válega; J. P. Coelho; C. B. Lopes; S. Rodrigues; A. Cachada; M. Otero; M. A. Pardal; A. C. Duarte (Environmental Monitoring and Assessment, 2009)

Characteristics and economic contribution of a developing recreational fishery in southern Angola - W. M. POTTS; A.‐R. CHILDS; W. H. H. SAUER; A. D. C. DUARTE (Fisheries Management and Ecology, 2009)
The characteristics and contribution of a developing recreational fishery to the local, regional and national economy of Angola were evaluated in 2006. Annual angling effort was 13 435 h, while the estimated total catch of the three target species [leerfish, Lichia amia (L.), west coast dusky kob, Argyrosomus coronus (Griffiths & Heemstra) and shad, Pomatomus saltatrix (L.)], was 5913 fish with a mass of 27 975 kg. Catch per unit effort (CPUE) for all teleost species combined was 0.44 fish per angler h −1 and 2.08 kg per angler h −1 . Total harvest of the three species was 576 fish with a total mass of 2221.6 kg. The total contribution of this recreational fishery (mostly anglers from South Africa) to the local economy was US$ 1007 per harvested fish and US$ 243 per harvested kg. This equated to a contribution to the local, regional and national economies of US$ 151 685, US$ 44 767 and US$ 344 364 respectively. Although the regional contribution was less than half of the national contribution, it was regionally significant when the low population density and the general absence of other formal sector employment opportunities are considered. As a result of the largely undisturbed nature of the southern Angolan coastline, the catch, effort and CPUE information was considered suitable as a baseline for a cost‐effective method of future fisheries monitoring in the region.

Absorption and fluorescence properties of rainwater during the cold season at a town in Western Portugal - Patrícia S. M. Santos; Regina M. B. O. Duarte; Armando C. Duarte (Journal of Atmospheric Chemistry, 2009)

Metabolic activity interferometer: description and calibration of an interferometric method to measure growth of mycobacteria - R. R. P. Machado; E. S. Lima Filho; D. F. Jardim; M. A. A. Ferreira; C. G. de Faria; R. S. Duarte; B. Lesche (European Biophysics Journal, 2008)

Biogeochemical modelling of Ria Formosa (South Portugal) - P. Duarte; B. Azevedo; M. Guerreiro; C. Ribeiro; R. Bandeira; A. Pereira; M. Falcão; D. Serpa; J. Reia (Hydrobiologia, 2008)

The Charisma of Coastal Ecosystems: Addressing the Imbalance - Carlos M. Duarte; William C. Dennison; Robert J. Orth; Tim J. B. Carruthers (Estuaries and Coasts, 2008)

Evaluation of the microbial diversity in a horizontal-flow anaerobic immobilized biomass reactor treating linear alkylbenzene sulfonate - I. C. S. Duarte; L. L. Oliveira; N. K. D. Saavedra; F. Fantinatti-Garboggini; V. M. Oliveira; M. B. A. Varesche (Biodegradation, 2008)

First assessment of microbial diversity in faecal microflora of Eurasian otter (Lutra lutra Linnaeus, 1758) in Portugal - M. Oliveira; T. Sales-Luís; A. Duarte; S. F. Nunes; C. Carneiro; T. Tenreiro; R. Tenreiro; M. Santos-Reis; L. Tavares; C. L. Vilela (European Journal of Wildlife Research, 2008)

The Charisma of Coastal Ecosystems: Addressing the Imbalance - Carlos M. Duarte; William C. Dennison; Robert J. W. Orth; Tim J. B. Carruthers (Estuaries and Coasts, 2008)

Evaluation of tests to assess the quality of mine-contaminated soils - P. Alvarenga; P. Palma; A. P. Gonçalves; R. M. Fernandes; A. de Varennes; G. Vallini; E. Duarte; A. C. Cunha-Queda (Environmental Geochemistry and Health, 2008)

Treatment of Acid Mine Drainage by Sulphate-reducing Bacteria Using Low Cost Matrices - M. C. Costa; M. Martins; C. Jesus; J. C. Duarte (Water, Air, & Soil Pollution, 2008)

Standardizing methods to address clonality in population studies - S. ARNAUD‐HAOND; C. M. DUARTE; F. ALBERTO; E. A. SERRÃO (Molecular Ecology, 2007)
Although clonal species are dominant in many habitats, from unicellular organisms to plants and animals, ecological and particularly evolutionary studies on clonal species have been strongly limited by the difficulty in assessing the number, size and longevity of genetic individuals within a population. The development of molecular markers has allowed progress in this area, and although allozymes remain of limited use due to their typically low level of polymorphism, more polymorphic markers have been discovered during the last decades, supplying powerful tools to overcome the problem of clonality assessment. However, population genetics studies on clonal organisms lack a standardized framework to assess clonality, and to adapt conventional data analyses to account for the potential bias due to the possible replication of the same individuals in the sampling. Moreover, existing studies used a variety of indices to describe clonal diversity and structure such that comparison among studies is difficult at best. We emphasize the need for standardizing studies on clonal organisms, and particularly on clonal plants, in order to clarify the way clonality is taken into account in sampling designs and data analysis, and to allow further comparison of results reported in distinct studies. In order to provide a first step towards a standardized framework to address clonality in population studies, we review, on the basis of a thorough revision of the literature on population structure of clonal plants and of a complementary revision on other clonal organisms, the indices and statistics used so far to estimate genotypic or clonal diversity and to describe clonal structure in plants. We examine their advantages and weaknesses as well as various conceptual issues associated with statistical analyses of population genetics data on clonal organisms. We do so by testing them on results from simulations, as well as on two empirical data sets of microsatellites of the seagrasses Posidonia oceanica and Cymodocea nodosa . Finally, we also propose a selection of new indices and methods to estimate clonal diversity and describe clonal structure in a way that should facilitate comparison between future studies on clonal plants, most of which may be of interest for clonal organisms in general.

Xylitol production by Debaryomyces hansenii in brewery spent grain dilute-acid hydrolysate: effect of supplementation - Florbela Carvalheiro; Luís C. Duarte; Raquel Medeiros; Francisco M. Gírio (Biotechnology Letters, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Spatial and temporal variation in the elemental and stable isotopic content of the seagrasses Posidonia oceanica and Cymodocea nodosa from the Illes Balears, Spain - J. W. Fourqurean; N. Marbà; C. M. Duarte; E. Diaz-Almela; S. Ruiz-Halpern (Marine Biology, 2007)

Large‐scale variability in surface bacterial carbon demand and growth efficiency in the subtropical northeast Atlantic Ocean - Laura Alonso-Sáez; Josep M. Gasol; Javier Arístegui; Juan C. Vilas; Dolors Vaqué; Carlos M. Duarte; Susana Agustí (Limnology and Oceanography, 2007)
We present surface estimates of bacterial respiration, bacterial heterotrophic production (BHP), and bacterial growth efficiency (BGE), and their relationship with nutrient availability, along a trophic gradient from coastal upwelling waters to the open‐ocean waters of the eastern North Atlantic. Bacterial respiration generally ranged between 10 and 30 µg C L −1 d −1 and was relatively unaffected by nutrient enrichment. In contrast, BHP showed higher variability (more than one order‐of‐magnitude range) and was affected by carbon and/or phosphorus additions in different regions. Empirical bacterial carbon‐to‐leucine (Leu) conversion factors (CFs) (range, 0.02–1.29 kg C mol Leu −1 ) decreased from the coast to the open ocean, largely influencing the BHP estimates in oligotrophic waters. We found high percentages of Leu respiration in oceanic waters (average 68% of Leu taken up by bacteria), possibly related to the low CFs found offshore. Empirical CFs were highly correlated to BGE (Pearson correlation coefficient r = 0.86, n = 12, p

Plumbing the Global Carbon Cycle: Integrating Inland Waters into the Terrestrial Carbon Budget - J. J. Cole; Y. T. Prairie; N. F. Caraco; W. H. McDowell; L. J. Tranvik; R. G. Striegl; C. M. Duarte; P. Kortelainen; J. A. Downing; J. J. Middelburg; J. Melack (Ecosystems, 2007)

Genetic diversity of three endangered species of Echium L. (Boraginaceae) endemic to Cape Verde Islands - Maria M. Romeiras; Helena C. Cotrim; Maria C. Duarte; Maria S. Pais (Biodiversity and Conservation, 2007)

Molecular characterization and antimicrobial activity of endophytic fungi from coffee plants - L. D. Sette; M. R. Z. Passarini; C. Delarmelina; F. Salati; M. C. T. Duarte (World Journal of Microbiology and Biotechnology, 2006)

Genetic structure at range edge: low diversity and high inbreeding in Southeast Asian mangrove ( Avicennia marina ) populations - S. ARNAUD‐HAOND; S. TEIXEIRA; S. I. MASSA; C. BILLOT; P. SAENGER; G. COUPLAND; C. M. DUARTE; E. A. SERRÃO (Molecular Ecology, 2006)
Understanding the genetic composition and mating systems of edge populations provides important insights into the environmental and demographic factors shaping species’ distribution ranges. We analysed samples of the mangrove Avicennia marina from Vietnam, northern Philippines and Australia, with microsatellite markers. We compared genetic diversity and structure in edge (Southeast Asia, and Southern Australia) and core (North and Eastern Australia) populations, and also compared our results with previously published data from core and southern edge populations. Comparisons highlighted significantly reduced gene diversity and higher genetic structure in both margins compared to core populations, which can be attributed to very low effective population size, pollinator scarcity and high environmental pressure at distribution margins. The estimated level of inbreeding was significantly higher in northeastern populations compared to core and southern populations. This suggests that despite the high genetic load usually associated with inbreeding, inbreeding or even selfing may be advantageous in margin habitats due to the possible advantages of reproductive assurance, or local adaptation. The very high level of genetic structure and inbreeding show that populations of A. marina are functioning as independent evolutionary units more than as components of a metapopulation system connected by gene flow. The combinations of those characteristics make these peripheral populations likely to develop local adaptations and therefore to be of particular interest for conservation strategies as well as for adaptation to possible future environmental changes.

Determination of Organic Mercury in Biota, Plants and Contaminated Sediments Using a Thermal Atomic Absorption Spectrometry Technique - M. Válega; S. Abreu; P. Pato; L. Rocha; A. R. Gomes; M. E. Pereira; A. C. Duarte (Water, Air, & Soil Pollution, 2006)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2006)

A comparative study of responses in plankton food web structure and function in contrasting European coastal waters exposed to experimental nutrient addition - Y. Olsen; S. Agustí; T. Andersen; C. M. Duarte; J. M. Gasol; I. Gismervik; A.-S. Heiskanen; E. Hoell; P. Kuuppo; R. Lignell; H. Reinertsen; U. Sommer; et al. (Limnology and Oceanography, 2006)
We quantify, compare, and generalize responses of experimental nutrient loadings (L N ) on planktonic community structure and function in coastal waters. Data were derived from three mesocosm experiments undertaken in Baltic (BAL), Mediterranean (MED), and Norwegian (NOR) coastal waters. A planktonic model with seven functional compartments and 30–32 different carbon flows fit to all three experiments was used as a framework for flow‐rate estimation and comparison. Flows were estimated on the basis of time series of measured biomass, some measured flows, and inverse modeling. Biomass and gross uptake rate of carbon of most groups increased linearly with increasing L N in the nutrient input range of 0–1 µmol N L −1 d −1 at all locations. The fate of the gross primary production (GPP) was similar in all systems. Autotrophic biomass varied by two orders of magnitude among locations, with the lowest biomass and response to nutrient addition in MED waters. The variation of GPP among sites was less than one order of magnitude. Mesozooplankton dominated by doliolids (Tunicata), but not those dominated by copepods, presumably exerted efficient control of the autotrophic biomass, thereby buffering responses of autotrophs to high nutrient input. Among the many factors that can modify the responses of autotrophs to nutrients, the time scale over which the enrichment is made and the precise mode of nutrient enrichment are important. We suggest a general concept that may contribute to a scientific basis for understanding and managing coastal eutrophication.

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE-Brazil II. Spatial and ontogenetic dynamics in Andira legalis, a deciduous legume tree - A. Geβler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; F. R. Scarano; H. L. T. Zaluar; H. Rennenberg (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE Brazil I. Performance of three different species of Clusia in an array of plant communities - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; H. L. T. Zaluar; U. Lüttge (Trees, 2005)

Ecophysiology of selected tree species in different plant communities at the periphery of the Atlantic Forest of SE—Brazil III. Three legume trees in a semi-deciduous dry forest - A. Geßler; H. M. Duarte; A. C. Franco; U. Lüttge; E. A. de Mattos; M. Nahm; P. J. F. P. Rodrigues; F. R. Scarano; H. Rennenberg (Trees, 2005)

Physiological synecology of tree species in relation to geographic distribution and ecophysiological parameters at the Atlantic forest periphery in Brazil: an overview - F. R. Scarano; H. M. Duarte; A. C. Franco; A. Geβler; E. A. de Mattos; H. Rennenberg; U. Lüttge (Trees, 2005)

Bioremediation of Acid Mine Drainage Using Acidic Soil and Organic Wastes for Promoting Sulphate-Reducing Bacteria Activity on a Column Reactor - M. C. Costa; J. C. Duarte (Water, Air, & Soil Pollution, 2005)

In situ measurements of carbon and nitrogen distribution and composition, photochemical efficiency and stable isotope ratios in Araucaria angustifolia - A. C. Franco; H. M. Duarte; A. Geβler; E. A. de Mattos; M. Nahm; H. Rennenberg; K. T. Ribeiro; F. R. Scarano; U. Lüttge (Trees, 2005)

Application of Non-Ionic Solid Sorbents (XAD Resins) for the Isolation and Fractionation of Water-Soluble Organic Compounds from Atmospheric Aerosols - Regina M. B. O. Duarte; Armando C. Duarte (Journal of Atmospheric Chemistry, 2005)

Population age structure and rhizome growth of Cymodocea nodosa in the Ria Formosa (southern Portugal) - A. H. Cunha; C. M. Duarte (Marine Biology, 2005)

Effect of a high-altitude expedition to a Himalayan peak (Pumori, 7,161m) on plasma and erythrocyte antioxidant profile - Jos Magalhes; Antnio Ascenso; Franklim Marques; Jos M. C. Soares; Rita Ferreira; Maria J. Neuparth; Jos A. Duarte (European Journal of Applied Physiology, 2005)

Variation of Mercury Contamination in Chicks of Little Tern Sterna albifrons in Southwest Europe: Brood, Age, and Colony Related Effects - P. C. Tavares; L. R. Monteiro; R. J. Lopes; M. E. Pereira; A. C. Duarte; R. W. Furness (Bulletin of Environmental Contamination and Toxicology, 2005)

A case of eumycetoma due to Madurella grisea in northern Brazil - Raquel Vilela; Olga M. V. Duarte; Carlos A. Rosa; Joao G. F. Castro; Sandra Lyon; Roberta L. Motta; Ana C. L. Moura (Mycopathologia, 2004)

Acute and severe hypobaric hypoxia-induced muscle oxidative stress in mice: the role of glutathione against oxidative damage - Jos Magalhes; Jos M. C. Soares; Maria J. Neuparth; Rita Ferreira; Jos Oliveira; Francisco Amado; Jos A. Duarte; Antnio Ascenso (European Journal of Applied Physiology, 2004)

Ca2+ and the bacterial peroxidases: the cytochrome c peroxidase from Pseudomonas stutzeri - Cristina G. Timóteo; Pedro Tavares; Celia F. Goodhew; Luís C. Duarte; Kornelia Jumel; Francisco M. Gírio; Steven Harding; Graham W. Pettigrew; Isabel Moura (JBIC Journal of Biological Inorganic Chemistry, 2003)

Effects of melatonin on orofacial movements in rats - Abílio V.; Vera J.; Ferreira L.; Duarte C.; Carvalho R.; Grassl C.; Martins C.; Torres-Leite D.; Bignotto M.; Tufik S.; de Ribeiro; Frussa-Filho R. (Psychopharmacology, 2002)

Age and growth of the fan mussel Pinna nobilis from south-east Spanish Mediterranean seagrass ( Posidonia oceanica ) meadows - C. A. Richardson; H. Kennedy; C. M. Duarte; D. P. Kennedy; S. V. Proud (Marine Biology, 1999)

Nitrate uptake and diffusive nitrate supply in the Central Atlantic - Dolors Planas; Susana Agustí; Carlos M. Duarte; Tim C. Granata; Martín Merino (Limnology and Oceanography, 1999)
The latitudinal variation (35° to 28°N) in the rate of diffusive nitrate supply across the thermocline and the associated variation in the uptake rate of nitrate and ammonium in the Central Atlantic was studied. The calculated diffusive nitrate flux showed a sharp latitudinal gradient, with the lowest nitrate supply (0.00037 μ mol m −3 d −1 ) in the South Atlantic subtropical gyre and the highest values (23.5 μ mol m −3 d −1 ) between the Equator and 15°N. The uptake rate of nitrate was inhibited at high irradiance at most stations. Both nitrate and ammonium uptake rates were lowest (about 3 and 10 umol m −3 d −1 , respectively) at the southern end of the transect and increased (about 20 and 55 μ mol m −3 d −1 , respectively) towards the Equator, with this increase being much greater for ammonium than for nitrate uptake. The f ‐ratio was highest (≈0.4) just south of the Equator and lowest (≈0.03) at the southern end of the transect. The slope between total uptake rate of dissolved inorganic nitrogen and gross primary production, calculated from O 2 ‐based measurements, in surface waters (4.72 ± 1.54) was somewhat lower, but not significantly so, than the expected C/N ratio of 6.6. The average uptake rate of nitrate did not differ significantly from the average estimated diffusive supply of nitrate to the biogenic layer over the Central Atlantic. However, the nitrate uptake rate increased as the ⅓ power of the diffusive nitrate flux to the biogenic layer. As a result, nitrate uptake far exceeded (by up to 100‐fold) the nitrate flux to the biogenic layer in the stations where the supply of nitrate was lowest. The excess nitrate uptake averaged 0.65 ± 0.24 mmol NO 3 m −2 d −1 (range, 0.05–1.9 mmol NO 3 m −2 d −1 ), which must be supplied through atmospheric deposition and other perturbation events. This excess nitrate uptake is relatively large compared to the diffusive supply in the most unproductive areas, where external nitrate inputs fuel the new production. In contrast, these sources of nitrate are far less significant where high diffusive fluxes suffice to maintain high nitrate uptake rates.

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Some properties of eucalyptus kraft pulp treated with xylanase from Aspergillus niger - C. Máximo; M. Costa-Ferreira; J. Duarte (World Journal of Microbiology and Biotechnology, 1998)

Conservation genetics of the endangered Pampas deer ( Ozotoceros bezoarticus ) - S. GONZÁLEZ; J. E. MALDONADO; J. A. LEONARD; C. VILÀ; J. M. BARBANTI DUARTE; M. MERINO; N. BRUM‐ZORRILLA; R. K. WAYNE (Molecular Ecology, 1998)
The Pampas deer ( Ozotoceros bezoarticus L. 1758) is the most endangered neotropical cervid, and in the past occupied a wide range of open habitats including grassland, pampas, savanna, and cerrado (Brazil) from 5° to 41° S. To better understand the effect of habitat fragmentation on gene flow and genetic variation, and to uncover genetic units for conservation, we examined DNA sequences from the mitochondrial control region of 54 individuals from six localities distributed throughout the present geographical range of the Pampas deer. Our results suggest that the control region of the Pampas deer is one of the most polymorphic of any mammal. This remarkably high variability probably reflects large historic population sizes of millions of individuals in contrast to numbers of fewer than 80 000 today. Gene flow between populations is generally close to one migrant per generation and, with the exception of two populations from Argentina, all populations are significantly differentiated. The degree of gene flow was correlated with geographical distance between populations, a result consistent with limited dispersal being the primary determinant of genetic differentiation between populations. The molecular genetic results provide a mandate for habitat restoration and reintroduction of Pampas deer so that levels of genetic variation can be preserved and historic patterns of abundance can be reconstructed. However, the source of individuals for reintroduction generally should be from populations geographically closest to those now in danger of extinction.

Assessment and comparison of the Marennes-Oléron Bay (France) and Carlingford Lough (Ireland) carrying capacity with ecosystem models - C. Bacher; P. Duarte; J.G. Ferreira; M. Héral; O. Raillard (Aquatic Ecology, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Seasonal variability in mercury inputs into the Ria de Aveiro, Portugal - M. E. Pereira; A. C. Duarte; G. E. Millward (Aquatic Ecology, 1995)